Optical laminate

By designing a structure containing an active energy ray curable composition and a low glass transition temperature bonding layer in the optical laminate, the unevenness of the polymerizable liquid crystal compound in the humid and heat environment is solved, and the high humidity heat of the optical laminate is achieved Durability.

CN119487425APending Publication Date: 2025-02-18SUMITOMO CHEM CO LTD
View PDF 18 Cites 0 Cited by

Patent Information

Application Number
CN202280098012.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-29
Filing Date
2022-08-03
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the prior art, the liquid crystal polarizer and the liquid crystal phase difference layer formed using polymerizable liquid crystal compounds are prone to island-like unevenness in humid and heat environments, which affects the humidity and heat durability of the optical laminate.

Method used

An optical laminate structure is designed, including a protective layer, a liquid crystal polarizer, a first bonding layer, a first liquid crystal phase difference layer, a second bonding layer, a second liquid crystal phase difference layer and a third bonding layer, wherein The liquid crystal polarizer and the liquid crystal phase difference layer contain polymerizable liquid crystal compounds. The first bonding layer is a cured product layer of the active energy ray curable composition. The glass transition temperature of the second bonding layer and the third bonding layer is 25. Below ℃.

Benefits of technology

Through this structure, the humidity and heat durability of the optical laminate is significantly improved, and the unevenness of the liquid crystal polarizer and the liquid crystal phase difference layer are prevented in a humid and heat environment, and optical performance is maintained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119487425A_ABST
    Figure CN119487425A_ABST
Patent Text Reader

Abstract

The purpose of the present invention is to achieve excellent wet heat durability in an optical laminate provided with a liquid crystal polarizing plate and a liquid crystal phase difference layer formed using a polymerizable liquid crystal compound. The optical laminate includes a protective layer, a liquid crystal polarizer, a first bonding layer, a first liquid crystal phase difference layer, a second bonding layer, a second liquid crystal phase difference layer, and a third bonding layer in this order. The liquid crystal polarizing plate includes a cured product layer of a first liquid crystal composition containing a dichroic dye and a polymerizable liquid crystal compound. The first bonding layer is a cured product layer of an active energy ray-curable composition. The first liquid crystal phase difference layer and the second liquid crystal phase difference layer each comprise a cured product layer of a second liquid crystal composition containing a polymerizable liquid crystal compound. The glass transition temperatures of the second bonding layer and the third bonding layer are both 25 DEG C or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an optical layered body. Background Art

[0002] As an organic EL display device, a flexible display device that can be bent or rolled up to display a screen is known. In order to suppress the reflection of external light, a circular polarization plate stacked with a polarization element and a phase difference element is used in an organic EL display device. The circular polarization plate used in a flexible display device is required to reduce the reduction in optical properties of the bent portion and not easily cracked due to bending (for example, Patent Document 1, etc.).

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: International Publication No. 2016 / 158300 Summary of the invention

[0006] Problems to be solved by the invention

[0007] If the circular polarizing plate is thinned, the thickness of the organic EL display device can be reduced, and the bendability of the organic EL display device can be easily improved. Therefore, sometimes a liquid crystal polarizer and a liquid crystal phase difference layer formed by a liquid crystal compound are used as the polarizing element and phase difference element constituting the circular polarizing plate instead of the resin film, so as to make the circular polarizing plate thinner. However, if the circular polarizing plate having a liquid crystal polarizer and a liquid crystal phase difference layer is exposed to a hot and humid environment, sometimes an island-like unevenness (shading) is observed in the circular polarizing plate.

[0008] An object of the present invention is to achieve excellent wet heat durability in an optical laminate including a liquid crystal polarizing plate and a liquid crystal retardation layer formed using a polymerizable liquid crystal compound.

[0009] Means for solving problems

[0010] The present invention provides the following optical layered body.

[0011] [1] An optical laminate comprising, in order, a protective layer, a liquid crystal polarizing plate, a first bonding layer, a first liquid crystal retardation layer, a second bonding layer, a second liquid crystal retardation layer, and a third bonding layer,

[0012] The liquid crystal polarizing plate comprises a cured layer of a first liquid crystal composition containing a dichroic dye and a polymerizable liquid crystal compound.

[0013] The first liquid crystal retardation layer and the second liquid crystal retardation layer both include a cured layer of a second liquid crystal composition containing a polymerizable liquid crystal compound.

[0014] The first laminating layer is a cured layer of an active energy ray-curable composition.

[0015] The glass transition temperatures of the second bonding layer and the third bonding layer are both 25° C. or lower.

[0016] [2] The optical layered body according to [1], wherein the first bonding layer is a cured layer of a radically polymerizable adhesive composition.

[0017] [3] The optical laminate according to [1] or [2], wherein the thickness of the protective layer, the liquid crystal polarizing plate, the first liquid crystal retardation layer, and the second liquid crystal retardation layer are all less than 20.0 μm.

[0018] [4] The optical laminate according to any one of [1] to [3], wherein, when the distance from the surface of the protective layer on the side opposite to the liquid crystal polarizer to the surface of the third bonding layer on the side opposite to the second liquid crystal retardation layer is D1 [μm],

[0019] The total thickness D2 [μm] of the second bonding layer and the third bonding layer is 40% to 70% of D1.

[0020] [5] The optical layered body according to any one of [1] to [4], further comprising an overcoat layer (second protective layer) covering the surface of the liquid crystal polarizer on the first bonding layer side.

[0021] Effects of the Invention

[0022] According to the present invention, it is possible to provide an optical laminate including a liquid crystal polarizing plate and a liquid crystal retardation layer formed using a polymerizable liquid crystal compound and having excellent wet heat durability. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a cross-sectional view schematically showing an example of the optical layered body according to the embodiment of the present invention.

[0024] Figure 2 This is a schematic diagram for explaining the method of the bendability test in the example.

[0025] Figure 3 It is a schematic perspective view schematically showing an end surface processing device used in Examples. DETAILED DESCRIPTION

[0026] Hereinafter, preferred embodiments of the optical layered body will be described with reference to the drawings.

[0027] (Optical laminate)

[0028] Figure 1Schematic cross-sectional view of an example of an optical laminate according to an embodiment of the present invention. Figure 1 As shown, the optical laminate 1 includes a protective layer 11, a liquid crystal polarizer 15, a first bonding layer 31, a first liquid crystal phase difference layer 21, a second bonding layer 32, a second liquid crystal phase difference layer 22, and a third bonding layer 33 in order. The optical laminate 1 may further include an outer coating layer (second protective layer) 18 covering the surface of the first bonding layer 31 side of the liquid crystal polarizer 15. In the optical laminate 1, when the outer coating layer 18 is not included, the protective layer 11 and the liquid crystal polarizer 15 can constitute the polarizing plate 10, and when the outer coating layer 18 is included, the protective layer 11, the liquid crystal polarizer 15 and the outer coating layer 18 can constitute the polarizing plate 10. The polarizing plate has the function of absorbing polarized light components parallel to the absorption axis and transmitting polarized light components orthogonal to the absorption axis. On the opposite side of the third bonding layer 33 of the optical laminate 1 to the second liquid crystal phase difference layer 22 side, a spacer 38 that can be peeled off relative to the third bonding layer 33 can be bonded. The optical layered body 1 and the spacer 38 constitute an optical layered body with a spacer.

[0029] In the optical laminate 1, it is preferred that the first laminating layer 31 is in direct contact with the polarizing plate 10 and the first liquid crystal phase difference layer 21, the second laminating layer 32 is in direct contact with the first liquid crystal phase difference layer 21 and the second liquid crystal phase difference layer 22, and the third laminating layer 33 is in direct contact with the second liquid crystal phase difference layer 22. The first laminating layer 31 may be in direct contact with the liquid crystal polarizer 15 constituting the polarizing plate 10, or may be in direct contact with the outer coating layer 18 constituting the polarizing plate 10. In the polarizing plate 10, it is preferred that the protective layer 11 is in direct contact with the liquid crystal polarizer 15, and it is preferred that the liquid crystal polarizer 15 is in direct contact with the outer coating layer 18.

[0030] The protective layer 11 may constitute the outermost surface of the viewing side of the optical laminate 1, and may cover and protect the surface of the liquid crystal polarizer 15. The surface of the protective layer 11 opposite to the liquid crystal polarizer 15 side is usually a surface exposed to the atmosphere, a surface covered by a surface protective film (protective film) that can be peeled off from the surface of the protective layer 11, or a surface covered by an adhesive layer having a thickness of 50 μm or more for bonding the front panel. In other words, in the protective layer 11, the layer existing in the range from the surface of the liquid crystal polarizer 15 on the protective layer 11 side to the above-mentioned surface of the protective layer 11 constitutes the protective layer 11.

[0031] The protective layer 11 may have a single-layer structure or a multi-layer structure. The protective layer 11 preferably includes a resin layer. The protective layer 11 may include, for example, a part or all of a first substrate layer (described later) on which a first liquid crystal composition (described later) for forming a liquid crystal polarizer 15 is applied. The details of the protective layer 11 will be described later.

[0032] The liquid crystal polarizer 15 includes a cured layer of a first liquid crystal composition containing a dichroic pigment and a polymerizable liquid crystal compound. By making the liquid crystal polarizer 15 a cured layer of the first liquid crystal composition, the thickness of the liquid crystal polarizer 15 can be reduced compared to a polarizer obtained by adsorption and orientation of the dichroic pigment on a polyvinyl alcohol resin film, so that the optical laminate 1 can be thinned. The liquid crystal polarizer 15 may have a single-layer structure formed only by the above-mentioned cured layer, or may have a multilayer structure including a first orientation film for orienting a polymerizable liquid crystal compound (described later) contained in the first liquid crystal composition on the basis of the above-mentioned cured layer. The details of the liquid crystal polarizer 15 will be described later.

[0033] The first liquid crystal phase difference layer 21 and the second liquid crystal phase difference layer 22 both include a cured layer of a second liquid crystal composition containing a polymerizable liquid crystal compound. By making the first liquid crystal phase difference layer 21 and the second liquid crystal phase difference layer 22 a cured layer of a second liquid crystal composition, the thickness of the first liquid crystal phase difference layer 21 and the second liquid crystal phase difference layer 22 can be reduced compared to a phase difference layer using a resin film, so that the optical laminate 1 can be thinned. The first liquid crystal phase difference layer 21 and the second liquid crystal phase difference layer 22 can have a single-layer structure formed only by the above-mentioned cured layer, or a multilayer structure including a second orientation film for orienting the polymerizable liquid crystal compound on the basis of the above-mentioned cured layer. The first liquid crystal phase difference layer 21 and the second liquid crystal phase difference layer 22 can include a cured layer formed by the same second liquid crystal composition as each other, or can include cured layers of second liquid crystal compositions that are different from each other.

[0034] The first laminating layer 31 is a cured layer of an active energy ray-curable composition. In the optical laminate 1, the liquid crystal polarizer 15 is a cured layer of a first liquid crystal composition, and the first liquid crystal phase difference layer 21 and the second liquid crystal phase difference layer 22 are cured layers of a second liquid crystal composition. Therefore, the thickness of the liquid crystal polarizer 15, the first liquid crystal phase difference layer 21, and the second liquid crystal phase difference layer 22 can be reduced, and the optical laminate 1 can be made thinner.

[0035] By making the first laminating layer 31 a cured layer of an active energy ray curable composition, when the optical laminate 1 is exposed to a hot and humid environment, the transmittance of the transmitted light parallel to the transmission axis direction can be suppressed from decreasing, so that the observation of island-like unevenness (shading) in the optical laminate 1 can be suppressed. The reason is considered to be as follows. The cured layer of the active energy ray curable composition has a large crosslinking density compared to the laminating layer (hereinafter also referred to as the "adhesive layer") having a glass transition temperature of 25°C or less. Therefore, in the cured layer of the active energy ray curable composition, it is easy to suppress the diffusion of the dichroic dye contained in the liquid crystal polarizer 15 to the layer on the side of the first liquid crystal phase difference layer 21 of the liquid crystal polarizer 15 compared to the adhesive layer, and the orientation disorder of the dichroic dye in the optical laminate 1 can be suppressed. As described above, in the optical laminate 1 in which the first laminating layer 31 is a cured layer of an active energy ray curable composition, the reduction of the above-mentioned transmittance when exposed to a hot and humid environment can be suppressed. This can suppress observation of sea-island-like unevenness (shading) in the optical layered body 1 , and can provide the optical layered body 1 having excellent moisture and heat durability.

[0036] By using a cured layer of an active energy ray-curable composition as the first bonding layer 31, it is also possible to prevent damage from being left when a force is applied from the outside of the optical laminate 1, compared with the case of using an adhesive layer. In particular, when the thickness of the protective layer 11 of the optical laminate 1 is small (for example, when it is 15 μm or less), the first bonding layer 31 is preferably a cured layer of an active energy ray-curable composition in order to prevent damage from being generated in the optical laminate 1.

[0037] The active energy ray curable composition for forming the first laminating layer 31 is preferably a free radical polymerizable adhesive composition. That is, the first laminating layer 31 is preferably a cured layer of a free radical polymerizable adhesive composition. The free radical polymerizable adhesive composition forms a cross-linked structure through a curing reaction, so that the speed at which the hardness increases is fast, and a cured layer with sufficient hardness can be formed just after the active energy ray is irradiated. In contrast, the curing reaction of the cationic polymerizable adhesive composition is slowly advanced, so that uncured components remain just after the active energy ray is irradiated, and compared with the cured layer of the free radical polymerizable adhesive composition, there is a tendency that it is difficult to obtain a cured layer with sufficient hardness just after the active energy ray is irradiated. Therefore, it is believed that the cured layer of the free radical polymerizable adhesive composition is not easily deformed by the force received from the outside just after curing, and it is not easy to leave foreign matter bite marks in the optical laminate 1.

[0038] The optical laminate 1 is usually manufactured in the form of a long strip, so the layer bonded by the first bonding layer 31 is also a long strip. If such a long strip is transported using bonding rollers and transport rollers, there is a case where foreign matter bite marks are generated in the resulting optical laminate 1 due to contact with these rollers. If the first bonding layer 31 is a cured layer of a radical polymerizable adhesive composition as described above, sufficient hardness can be obtained even immediately after curing, so it is not easy to be deformed by a force applied from the outside, and the occurrence of foreign matter bite marks in the optical laminate 1 can be suppressed.

[0039] On the contrary, when the first laminating layer 31 is a cured layer of a cationic adhesive composition, it is easy to contact the laminating roller or the conveying roller without fully undergoing the curing reaction. Therefore, compared with the case where the first laminating layer 31 is a cured layer of a radical polymerizable adhesive composition, it is easy to generate foreign matter bite marks on the optical laminate 1. The details of the first laminating layer 31 are described later.

[0040] The second bonding layer 32 and the third bonding layer 33 are preferably bonding layers having a glass transition temperature (hereinafter, also referred to as "Tg") of 25°C or less. The bonding layer having a Tg of 25°C or less can be referred to as a so-called adhesive layer formed using an adhesive composition (pressure-sensitive adhesive). The third bonding layer 33 can be a bonding layer for bonding the optical laminate 1 to a display element of a display device. When the Tg of the third bonding layer 33 is 25°C or less, a spacer 38 can be bonded to the side of the third bonding layer 33 of the optical laminate 1 opposite to the side of the second liquid crystal phase difference layer 22.

[0041] like Figure 1 As shown, when the distance from the surface of the protective layer 11 on the side opposite to the liquid crystal polarizer 15 to the surface of the third bonding layer 33 on the side opposite to the second liquid crystal retardation layer 22 is set to D1 [μm], the total thickness Dt [μm] of the layer (adhesive layer) having a Tg of 25°C or less among the first bonding layer 31, the second bonding layer 32, and the third bonding layer 33 is preferably 40% or more and 70% or less of the distance D1, more preferably 40% or more and 67% or less, and may be 45% or more and 65% or less, or 50% or more and 65% or less. In the optical laminate 1, the layer (adhesive layer) having a Tg of 25°C or less among the first bonding layer 31, the second bonding layer 32, and the third bonding layer 33 is the second bonding layer 32 and the third bonding layer 33. Therefore, the total thickness Dt is equal to the total thickness D2 [μm] of the thickness of the second bonding layer 32 and the thickness of the third bonding layer 33. In this case, the total thickness D2 is preferably 40% to 70% of the distance D1, more preferably 40% to 67%, and may be 45% to 65%, or 50% to 65%.

[0042] The optical laminate 1 is easily bent due to the above-mentioned thinning, and therefore can be suitably used in a flexible display device that can realize bending and winding of the display screen. When the optical laminate 1 is applied to a flexible display device and bent, if the total thickness D2 is less than the above range, the third bonding layer 33 is easily broken due to the expansion and contraction of the third bonding layer 33 accompanying the bending. On the other hand, if the total thickness D2 of the second bonding layer 32 and the third bonding layer 33 is greater than the above range, cracks are easily generated in the first liquid crystal phase difference layer 21 and / or the second liquid crystal phase difference layer 22 during the grinding process of the optical laminate 1. If the optical laminate 1 is subjected to a processing impact, the second bonding layer 32 and the third bonding layer 33 whose Tg is below 25°C tend to be more easily deformed as their total thickness increases. It is considered that if the second laminating layer 32 and the third laminating layer 33 are greatly deformed, the first liquid crystal phase difference layer 21 and / or the second liquid crystal phase difference layer 22 are deformed accordingly, so that cracks are easily generated in the first liquid crystal phase difference layer 21 and / or the second liquid crystal phase difference layer 22. The details of the second laminating layer 32 and the third laminating layer 33 are described later.

[0043] In the optical laminate 1, the thickness of the protective layer 11, the liquid crystal polarizer 15, the first liquid crystal phase difference layer 21, and the second liquid crystal phase difference layer 22 are preferably less than 20.0 μm. The thickness of the protective layer 11, the liquid crystal polarizer 15, the first liquid crystal phase difference layer 21, and the second liquid crystal phase difference layer 22 is preferably less than 20.0 μm, and each independently is preferably 15.0 μm or less, more preferably 10.0 μm or less, further preferably 5.0 μm or less, further preferably less than 5.0 μm, particularly preferably 4.5 μm or less, and most preferably 4.0 μm or less, 3.5 μm or less, or 3.0 μm or less. The thickness of the protective layer 11, the liquid crystal polarizer 15, the first liquid crystal phase difference layer 21, and the second liquid crystal phase difference layer 22 is usually 0.01 μm or more, and can also be 0.1 μm or more. When the thickness of each layer is within the above range, it is easy to suppress the occurrence of unevenness in the reflected color tone of the bent portion when the optical layered body 1 is repeatedly bent.

[0044] The thickness of the protective layer 11 may be within the above range, but is preferably 0.1 μm or more and less than 20.0 μm, more preferably 0.1 μm or more and 10.0 μm or less, further preferably 0.1 μm or more and less than 5.0 μm, further preferably 0.1 μm or more and 4.5 μm or less, and most preferably 0.1 μm or more and 4.0 μm or less.

[0045] The thickness of the liquid crystal polarizing plate 15 may be within the above range, but is preferably 0.1 μm to 10.0 μm, more preferably 0.3 μm to 5.0 μm, and even more preferably 0.5 μm to 3.0 μm.

[0046] The thickness of the first liquid crystal retardation layer 21 and the second liquid crystal retardation layer 22 may be within the above range, and may be, for example, each independently preferably 0.1 μm to 10.0 μm, more preferably 0.3 μm to 5.0 μm, and further preferably 0.3 μm to 3.0 μm.

[0047] The optical layered body 1 may be a circularly polarizing plate. In this case, the optical layered body 1 can be used as an antireflection film.

[0048] (Method for producing optical laminate)

[0049] The optical laminate 1 can be manufactured by laminating a protective layer 11, a liquid crystal polarizer 15, a first laminating layer 31, a first liquid crystal phase difference layer 21, a second laminating layer 32, a second liquid crystal phase difference layer 22, and a third laminating layer 33. The order of laminating the layers is not particularly limited. For example, [i] a laminate having a protective layer 11 and a liquid crystal polarizer 15 is laminated via the first laminating layer 31, and a laminate having a first liquid crystal phase difference layer 21 and a second liquid crystal phase difference layer 22 is laminated via the second laminating layer 32 to obtain a laminate (phase difference body), and then the third laminating layer 33 is laminated, [ii] a laminate having a protective layer 11 and a liquid crystal polarizer 15 is laminated via the first laminating layer 31, and then the second liquid crystal phase difference layer 22 is laminated via the second laminating layer 32, and then the third laminating layer 33 is further laminated.

[0050] (Display device)

[0051] The optical laminate 1 can be applied to a display device. The display device includes the optical laminate 1 and a display element, and the optical laminate 1 is disposed on the viewing side of the display element. The optical laminate 1 can be bonded to the display element using the third bonding layer 33 .

[0052] The display device is not particularly limited, and examples thereof include organic electroluminescent (organic EL) display devices, inorganic electroluminescent (inorganic EL) display devices, liquid crystal display devices, and electroluminescent display devices. When the optical laminate 1 is a circular polarizing plate, it can be suitably used as an antireflection film of an organic EL display device. The optical laminate 1 can be suitably used in a flexible display device that can realize bending and winding of a display screen.

[0053] The display device can be used as mobile devices such as smartphones and tablets, televisions, digital photo frames, electronic billboards, measuring instruments or measuring instruments, office equipment, medical equipment, electronic computer equipment, etc.

[0054] Hereinafter, details of each member constituting the optical layered body and a member for producing each layer will be described.

[0055] (Polarizing Plate)

[0056] The polarizing plate is a film including a liquid crystal polarizer and is a film that exerts the optical function of the liquid crystal polarizer. The polarizing plate may be a single liquid crystal polarizer, a laminated body in which a liquid crystal polarizer and a protective layer are directly laminated, or a laminated body in which a protective layer, a liquid crystal polarizer, and an outer coating layer (second protective layer) are directly laminated.

[0057] The polarization performance of the polarizing plate can be measured using a spectrophotometer. For example, a device equipped with a prism polarizer in the spectrophotometer can be used to measure the transmittance (T1) in the transmission axis direction (direction perpendicular to the orientation) and the transmittance (T2) in the absorption axis direction (orientation direction) in the visible light range, i.e., the wavelength range of 380nm to 780nm using the double beam method. The polarization performance in the visible light range can be calculated as follows, that is, using the following formulas (Formula 1) and (Formula 2), the single transmittance and polarization degree at each wavelength are calculated, and then the visibility is corrected using the 2-degree field of view (C light source) of JIS Z 8701, thereby calculating the visibility-corrected single transmittance (Ty) and the visibility-corrected polarization degree (Py). In addition, L is calculated using the isochromatic function of the C light source based on the transmittance measured in the same way. a b Chromaticity a in the (CIE) color system and b , thus obtaining the color tone of the polarizing plate alone (single color tone), the color tone of the polarizing plates arranged in parallel (parallel color tone), and the color tone of the polarizing plates arranged orthogonally (orthogonal color tone). and b The closer the value is to 0, the more it can be judged as a neutral tone.

[0058] Single body transmittance [%] = (T1 + T2) / 2 (Formula 1)

[0059] Polarization degree [%] = [(T1-T2) / (T1+T2)] × 100 (Formula 2)

[0060] The visibility correction polarization degree Py of the polarizing plate is usually 80% or more, preferably 90% or more, more preferably 95% or more, further preferably 98% or more, particularly preferably 99% or more, and if it is 99.9% or more, it can be suitably used in a liquid crystal display device. Increasing the visibility correction polarization degree Py of the polarizing plate is conducive to improving the anti-reflection function of the optical laminate. If the visibility correction polarization degree Py is less than 80%, it is difficult to fully exert the anti-reflection function when using the optical laminate as an anti-reflection film.

[0061] The larger the visibility correction single transmittance Ty of the polarizing plate, the greater the clarity of the white display. However, from the relationship between (Formula 1) and (Formula 2) above, it can be seen that if the single transmittance becomes too large, there is a problem of reduced polarization degree. Therefore, the visibility correction single transmittance Ty is preferably 30% or more and 60% or less, more preferably 35% or more and 55% or less, further preferably 40% or more and 50% or less, and further preferably 40% or more and 45% or less. If the visibility correction single transmittance Ty is too large, the visibility correction polarization degree Py becomes too small, and it is difficult to fully exert the anti-reflection function when using the optical laminate as an anti-reflection film.

[0062] The polarizing plate can be obtained as follows, that is, [i] directly forming a liquid crystal polarizer on the first substrate layer as described below, and using the first substrate layer as a protective layer, thereby obtaining it, [ii] using a material having a resin film and a surface treatment layer formed thereon as the first substrate layer, forming a liquid crystal polarizer on the surface treatment layer, and then peeling off the resin film contained in the first substrate layer, and using the surface treatment layer as a protective layer, thereby obtaining it. Alternatively, [iii] the first substrate layer used when forming the liquid crystal polarizer can be peeled off and removed, and a protective layer can be laminated on the liquid crystal polarizer. In the case where the polarizing plate has an outer coating layer, it is sufficient to form the outer coating layer on the liquid crystal polarizer on the first substrate layer.

[0063] (Liquid crystal polarizer)

[0064] A liquid crystal polarizer is a film having an absorption axis and a transmission axis orthogonal thereto in a plane, absorbing a polarization component parallel to the absorption axis, and transmitting a polarization component parallel to the transmission axis. A liquid crystal polarizer is a film having the following structure, that is, a layer (cured material layer) of a polymer containing a polymerizable liquid crystal compound containing a dichroic dye alone, or a two-layer structure of the layer and an oriented film. In a liquid crystal polarizer, the dichroic dye is oriented in one direction in a plane. A liquid crystal polarizer can be formed as a material containing a layer (cured material layer) containing a polymer of a polymerizable liquid crystal compound containing a dichroic dye by uniaxially oriented the dichroic dye and the polymerizable liquid crystal compound from a first liquid crystal composition containing a polymerizable liquid crystal compound and a dichroic dye. That is, a liquid crystal polarizer can exhibit a polarization function by utilizing the dichroic dye contained in the polymer of the polymerizable liquid crystal compound to anisotropically absorb light.

[0065] The liquid crystal polarizer including the cured layer of the first liquid crystal composition can be suitably used in, for example, a flexible display device because the color tone can be arbitrarily controlled, the thickness can be greatly reduced, and there is basically no stretching relaxation caused by heat and it is non-contractile.

[0066] The ratio of the absorbance A1(λ) in the orientation direction of the liquid crystal polarizer for light of wavelength λ[nm] to the absorbance A2(λ) in the perpendicular direction in the orientation plane (dichroic ratio; A1(λ) / A2(λ)) is preferably 7 or more, more preferably 20 or more, and even more preferably 40 or more. The larger the value, the more it can be said that the liquid crystal polarizer has excellent absorption selectivity. Although it also depends on the type of dichroic dye, in the case of a cured layer obtained by curing in a nematic liquid crystal phase, the above ratio is about 5 to 10.

[0067] By making the liquid crystal polarizer contain two or more dichroic pigments with different absorption wavelengths, liquid crystal polarizers of various hues can be produced, and liquid crystal polarizers with absorption in the entire visible light range can be produced. By producing a liquid crystal polarizer with such absorption characteristics, it can be expanded to a variety of uses.

[0068] The liquid crystal polarizer can be formed by coating the first liquid crystal composition on the first substrate layer on which the first orientation film is formed as needed, and orienting the dichroic pigment contained in the first liquid crystal composition. The liquid crystal polarizer may further include a first orientation film on the basis of including a cured layer. The first substrate layer may be used directly as a protective layer, or the resin film included in the first substrate layer may be used as a protective layer, or the resin film may be peeled off and removed, and the surface treatment layer included in the first substrate layer may be used as a protective layer. The first orientation film may be peeled off and removed together with the resin film. The peeling and removal of the resin film and the first orientation film may be performed after the liquid crystal polarizer is stacked with the first liquid crystal phase difference layer and the second liquid crystal phase difference layer.

[0069] (First Liquid Crystal Composition)

[0070] The first liquid crystal composition is a composition for forming a liquid crystal polarizer, and may include a solvent, a leveling agent, a polymerization initiator, a sensitizer, a polymerization inhibitor, a crosslinking agent, a bonding agent, a reactive additive, and other additives in addition to the dichroic pigment and the polymerizable liquid crystal compound. From the viewpoint of processability, the first liquid crystal composition preferably includes a solvent and a leveling agent.

[0071] The so-called polymerizable liquid crystal compound is a compound having at least one polymerizable group in the molecule and having liquid crystal properties. The polymerizable group refers to a group participating in the polymerization reaction, preferably a photopolymerizable group. Here, the so-called photopolymerizable group refers to a group that can participate in the polymerization reaction using active free radicals, acids, etc. generated from the photopolymerization initiator described later. As polymerizable groups, vinyl, vinyloxy, 1-chlorovinyl, isopropenyl, 4-vinylphenyl, acryloyloxy, methacryloyloxy, oxirane, oxetane, etc. can be cited. Among them, acryloyloxy, methacryloyloxy, vinyloxy, oxirane and oxetane are preferred, and methacryloyloxy and acryloyloxy are more preferred. Liquid crystal properties can be thermotropic liquid crystals or lyotropic liquid crystals. When mixed with dichroic pigments described later, thermotropic liquid crystals are preferred. The polymerizable liquid crystal compound can be a monomer or a polymer obtained by polymerization of a dimer or more.

[0072] When the polymerizable liquid crystal compound contained in the first liquid crystal composition is a thermotropic liquid crystal, it can be a thermotropic liquid crystal compound showing a nematic liquid crystal phase, or it can be a thermotropic liquid crystal compound showing a smectic liquid crystal phase. From the viewpoint of obtaining a liquid crystal polarizer (cured material layer) with a large dichroic ratio, the liquid crystal state displayed by the polymerizable liquid crystal compound is preferably a smectic phase, and if it is a high-order smectic phase, it is more preferred from the viewpoint of high performance. Among them, a high-order smectic liquid crystal compound that forms a smectic B phase, a smectic D phase, a smectic E phase, a smectic F phase, a smectic G phase, a smectic H phase, a smectic I phase, a smectic J phase, a smectic K phase or a smectic L phase is more preferred, and a high-order smectic liquid crystal compound that forms a smectic B phase, a smectic F phase or a smectic I phase is further preferred. If the liquid crystal phase formed by the polymerizable liquid crystal compound is these high-order smectic phases, a liquid crystal polarizer (cured material layer) with high polarization performance can be manufactured. In addition, a liquid crystal polarizer (cured material layer) with high polarization performance like this can obtain Bragg peaks derived from high-order structures such as hexagonal phases and crystalline phases in X-ray diffraction measurement. The Bragg peak is a peak derived from a periodic structure of molecular orientation, and a layer having a period interval of 3 to 6 Å can be obtained. From the viewpoint of obtaining higher polarization characteristics, the cured layer included in the liquid crystal polarizer preferably contains a polymer of a polymerizable liquid crystal compound in which the polymerizable liquid crystal compound is oriented in a smectic phase.

[0073] As the polymerizable liquid crystal compound contained in the first liquid crystal composition, one kind can be used alone, or two or more kinds can be used in combination. The content of the polymerizable liquid crystal compound in the first liquid crystal composition is preferably 40% by mass or more and 99.9% by mass or less relative to the solid content of the first liquid crystal composition, more preferably 60% by mass or more and 99% by mass or less, and further preferably 70% by mass or more and 99% by mass or less. If the content of the polymerizable liquid crystal compound is within the above range, there is a tendency for the orientation of the polymerizable liquid crystal compound to become higher. It should be noted that in this specification, the so-called solid content refers to the total amount of the components after removing the solvent from the first liquid crystal composition.

[0074] The so-called dichroic pigment refers to a pigment having a property that the absorbance in the long axis direction of the molecule is different from the absorbance in the short axis direction. As a dichroic pigment, it is preferred to have the characteristic of absorbing visible light, and more preferably have a dichroic pigment with a maximum absorption wavelength (λmax) in the range of 380 to 680 nm. As such a dichroic pigment, for example, acridine pigments, oxazine pigments, cyanine pigments, naphthalene pigments, azo pigments and anthraquinone pigments can be cited, among which azo pigments are preferred. As azo pigments, monoazo pigments, disazo pigments, triazo pigments, tetrazo pigments and stilbene (Japanese: スチルベン) azo pigments can be cited, preferably disazo pigments and triazo pigments. Dichroic pigments can be used alone or in combination, but in order to obtain absorption in the entire range of visible light, it is preferred to use two or more dichroic pigments in combination, and more preferably to use three or more dichroic pigments in combination.

[0075] Examples of the azo dye include compounds represented by formula (Da).

[0076] T 1 -A 1 (-N = NA 2 ) p -N=NA 3 -T 2 (Da)

[0077] [In formula (Da),

[0078] A 1 , A 2 and A 3 each independently represents a 1,4-phenylene group which may have a substituent, a naphthalene-1,4-diyl group which may have a substituent, a benzoic acid phenyl group which may have a substituent, a 4,4'-stilbenyl group which may have a substituent, or a divalent heterocyclic group which may have a substituent,

[0079] T 1 and T 2 It represents an electron withdrawing group or an electron donating group, and is located at a position substantially 180° with respect to the azo bond plane.

[0080] p represents an integer of 0 to 4. When p is 2 or more, each A 2 They can be the same or different from each other.

[0081] In the range showing absorption in the visible light region, the -N=N- bond may be replaced by a -C=C-, -COO-, -NHCO-, or -N=CH- bond.]

[0082] The content of the dichroic pigment contained in the first liquid crystal composition (the total amount thereof when multiple types are included) is usually 1 to 60 parts by mass, preferably 1 to 40 parts by mass, and more preferably 1 to 20 parts by mass, relative to 100 parts by mass of the polymerizable liquid crystal compound, from the viewpoint of obtaining good light absorption characteristics. If the content of the dichroic pigment is less than this range, light absorption is insufficient and sufficient polarization performance cannot be obtained. If it is greater than this range, the orientation of the liquid crystal molecules may be hindered.

[0083] The first liquid crystal composition may contain a solvent. Generally, since the viscosity of the polymerizable liquid crystal compound is high, coating becomes easy by preparing the first liquid crystal composition dissolved in the solvent, and as a result, it is often easy to form a cured layer of the liquid crystal polarizer. As the solvent, a solvent that can completely dissolve the polymerizable liquid crystal compound is preferred, and a solvent that is inactive to the polymerization reaction of the polymerizable liquid crystal compound is preferred.

[0084] Examples of the solvent include alcohol solvents such as methanol, ethanol, ethylene glycol, isopropanol, propylene glycol, ethylene glycol methyl ether, ethylene glycol butyl ether, and propylene glycol monomethyl ether; ester solvents such as ethyl acetate, butyl acetate, ethylene glycol methyl ether acetate, γ-butyrolactone, propylene glycol methyl ether acetate, and ethyl lactate; ketone solvents such as acetone, methyl ethyl ketone, cyclopentanone, cyclohexanone, 2-heptanone, and methyl isobutyl ketone; aliphatic hydrocarbon solvents such as pentane, hexane, and heptane; aromatic hydrocarbon solvents such as toluene and xylene; nitrile solvents such as acetonitrile; ether solvents such as tetrahydrofuran and dimethoxyethane; chlorinated solvents such as chloroform and chlorobenzene; amide solvents such as dimethylacetamide, dimethylformamide, N-methyl-2-pyrrolidone, and 1,3-dimethyl-2-imidazolidinone, etc. These solvents may be used alone or in combination of two or more.

[0085] The content of the solvent is preferably 50 to 98% by mass relative to the total amount of the first liquid crystal composition. In other words, the content of the solid component in the first liquid crystal composition is preferably 2 to 50% by mass, and more preferably 5 to 30% by mass.

[0086] The first liquid crystal composition may contain a leveling agent. The so-called leveling agent is an additive that has the function of adjusting the fluidity of the composition and making the film obtained by coating the composition flatter. As the leveling agent, for example, organic modified silicone oil-based, polyacrylate-based and perfluoroalkyl-based leveling agents can be cited. Among them, polyacrylate-based leveling agents and perfluoroalkyl-based leveling agents are preferred.

[0087] When the first liquid crystal composition contains a leveling agent, the amount is preferably 0.01 to 5 parts by mass, more preferably 0.05 to 3 parts by mass, based on 100 parts by mass of the content of the polymerizable liquid crystal compound.

[0088] The first liquid crystal composition may contain a polymerization initiator. A polymerization initiator is a compound that can initiate a polymerization reaction of a polymerizable liquid crystal compound, etc. As the polymerization initiator, a photopolymerization initiator that generates active free radicals by the action of light is preferred from the viewpoint of being independent of the phase state of the thermotropic liquid crystal.

[0089] As long as the photopolymerization initiator is a compound capable of initiating a polymerization reaction of a polymerizable liquid crystal compound, a known photopolymerization initiator can be used. Specifically, a photopolymerization initiator capable of generating active free radicals or acids by the action of light can be cited, among which a photopolymerization initiator generating free radicals by the action of light is preferred. The photopolymerization initiator can be used alone or in combination of two or more.

[0090] As the photopolymerization initiator, a known photopolymerization initiator can be used. For example, as a photopolymerization initiator that generates active free radicals, self-cleaving benzoin compounds, acetophenone compounds, hydroxyacetophenone compounds, α-aminoacetophenone compounds, oxime ester compounds, acylphosphine oxide compounds, azo compounds, etc. can be used, and hydrogen-abstracting benzophenone compounds, alkylphenone compounds, benzoin ether compounds, benzyl ketal compounds, dibenzosuberone compounds, anthraquinone compounds, xanthone compounds, thioxanthone compounds, halogenated acetophenone compounds, dialkoxyacetophenone compounds, halogenated bisimidazole compounds, halogenated triazine compounds, triazine compounds, etc. can be used. As a photopolymerization initiator that generates an acid, iodonium salts and sulfonium salts can be used. From the viewpoint of excellent reaction efficiency at low temperature, self-cleavage type photopolymerization initiators are preferred, and acetophenone compounds, hydroxyacetophenone compounds, α-aminoacetophenone compounds, and oxime ester compounds are particularly preferred.

[0091] The content of the polymerization initiator in the first liquid crystal composition can be appropriately adjusted according to the type and amount of the polymerizable liquid crystal compound, but is generally 0.1 to 30 parts by mass, preferably 0.5 to 10 parts by mass, and more preferably 0.5 to 8 parts by mass relative to 100 parts by mass of the polymerizable liquid crystal compound. If the content of the polymerization initiator is within the above range, polymerization can be performed without disturbing the orientation of the polymerizable liquid crystal compound.

[0092] The first liquid crystal composition may contain a sensitizer. As the sensitizer, a photosensitizer is preferred. When the first liquid crystal composition contains a sensitizer, the polymerization reaction of the polymerizable liquid crystal compound contained in the first liquid crystal composition can be further promoted. The amount of the sensitizer used is preferably 0.1 to 30 parts by mass relative to 100 parts by mass of the content of the polymerizable liquid crystal compound.

[0093] From the viewpoint of stably carrying out the polymerization reaction, the first liquid crystal composition may contain a polymerization inhibitor. The polymerization inhibitor can be used to control the degree of the polymerization reaction of the polymerizable liquid crystal compound. When the first liquid crystal composition contains a polymerization inhibitor, the content of the polymerization inhibitor is preferably 0.1 to 30 parts by mass relative to 100 parts by mass of the content of the polymerizable liquid crystal compound.

[0094] (Protective layer)

[0095] The protective layer has the function of protecting the surface of the liquid crystal polarizer. The liquid crystal polarizer and the protective layer are directly stacked on each other. The so-called "direct stacking" here includes a method of stacking the liquid crystal polarizer using the self-adhesiveness of the protective layer, and a method of stacking the protective layer on the liquid crystal polarizer by curing the first liquid crystal composition for forming a cured layer of the liquid crystal polarizer applied to the protective layer formed with the first orientation film as needed. For the protective layer, in order to improve the adhesion with the liquid crystal polarizer, a surface activation treatment (such as corona treatment, etc.) can be implemented, and a thin layer such as a primer layer (also called an easy-adhesion layer) can also be formed.

[0096] The protective layer may be the first substrate layer for forming the liquid crystal polarizer, or may be a layer comprising a portion of the first substrate layer. The protective layer may have a single-layer structure or a multi-layer structure. The protective layer preferably comprises a resin layer. The resin layer may be a resin film and / or a surface treatment layer.

[0097] As the resin film, for example, a film having excellent transparency, mechanical strength, thermal stability, water barrier, isotropy, stretchability, etc. can be used. The resin film can be a thermoplastic resin film. As specific examples of the resin constituting such a resin film, cellulose resins such as triacetyl cellulose; polyester resins such as polyethylene terephthalate and polyethylene naphthalate; polyethersulfone resins; polysulfone resins; polycarbonate resins; polyamide resins such as nylon and aromatic polyamide; polyimide resins; chain polyolefin resins such as polyethylene, polypropylene, and ethylene-propylene copolymers; cyclic polyolefin resins (also referred to as norbornene resins) having a ring system or norbornene structure; (meth) acrylic resins such as polymethyl methacrylate; polyarylate resins; polystyrene resins; polyvinyl alcohol resins, and mixtures thereof. The resin film of this material can be easily obtained from the market. The resin may be a thermosetting resin or an ultraviolet curing resin such as a (meth) acrylic resin, a urethane resin, a (meth) acrylic urethane resin, an epoxy resin, a silicone resin, etc. In this specification, the term "(meth) acrylic resin" means at least one of acrylic resin and methacrylic resin. The same applies to (meth) acryloyl resin, etc.

[0098] Examples of the chain polyolefin-based resins include homopolymers of chain olefins such as polyethylene resins (polyethylene resins as homopolymers of ethylene, copolymers mainly composed of ethylene) and polypropylene resins (polypropylene resins as homopolymers of propylene, copolymers mainly composed of propylene), and copolymers containing two or more chain olefins.

[0099] Cyclic polyolefin resin is a general term for resins polymerized with cyclic olefin as a polymerization unit. Specific examples of cyclic polyolefin resins include ring-opening (co)polymers of cyclic olefins, addition polymers of cyclic olefins, copolymers of cyclic olefins and chain olefins such as ethylene and propylene (representatively random copolymers), and graft polymers obtained by modifying them with unsaturated carboxylic acids and their derivatives, and hydrogenated products thereof. Among them, it is preferable to use a norbornene resin using a norbornene monomer such as norbornene and a polycyclic norbornene monomer as the cyclic olefin.

[0100] Polyester resins are resins having an ester bond in the main chain, and are generally polycondensates of polycarboxylic acids or their derivatives and polyols. Examples include terephthalic acid, isophthalic acid, dimethyl terephthalate, dimethyl naphthalate, etc. As polyols, divalent diols can be used, and examples include ethylene glycol, propylene glycol, butanediol, neopentyl glycol, cyclohexanedimethanol, etc.

[0101] Cellulose ester resins are esters of cellulose and fatty acids. Specific examples of cellulose ester resins include cellulose triacetate, cellulose diacetate, cellulose tripropionate, and cellulose dipropionate. Copolymers having a plurality of polymerized units constituting these cellulose ester resins and resins in which a portion of the hydroxyl groups is modified with other substituents may also be mentioned. Among them, cellulose triacetate (triacetyl cellulose) is particularly preferred.

[0102] (Meth) acrylic resins are resins that have a compound having a (meth) acryloyl group as a main constituent monomer. Specific examples of (meth) acrylic resins include poly (meth) acrylic acid esters such as polymethyl methacrylate; methyl methacrylate-(meth) acrylic acid copolymers; methyl methacrylate-(meth) acrylic acid ester copolymers; methyl methacrylate-acrylic acid ester-(meth) acrylic acid copolymers; methyl (meth) acrylate-styrene copolymers (MS resins, etc.); copolymers of methyl methacrylate and a compound having an alicyclic hydrocarbon group (e.g., methyl methacrylate-cyclohexyl methacrylate copolymers, methyl methacrylate-norbornyl (meth) acrylic acid copolymers, etc.).

[0103] The polycarbonate resin includes a polymer obtained by bonding monomer units via a carbonate group. The polycarbonate resin may be a resin called a modified polycarbonate in which the polymer skeleton is modified, a copolymer polycarbonate, etc. Details of the polycarbonate resin are described in, for example, Japanese Patent Application Laid-Open No. 2012-31370.

[0104] The protective layer can be prepared by stretching the above-mentioned resin film (thermoplastic resin film). Examples of the stretching treatment include uniaxial stretching and biaxial stretching. Examples of the stretching direction include the mechanical flow direction (MD) of the unstretched film, the direction (TD) perpendicular thereto, and the direction oblique to the mechanical flow direction (MD).

[0105] The protective layer is arranged on the observation side relative to the liquid crystal polarizer, so in order to give the desired surface optical properties or other characteristics, it can include a resin film and a surface treatment layer provided on the surface of the resin film. Alternatively, the protective layer may not include a resin film, but include a surface treatment layer as a resin layer. In the case where the protective layer does not include a resin film but includes a surface treatment layer, for example, the protective layer as a surface treatment layer can be laminated on the liquid crystal polarizer as shown below. First, the surface of the side of the resin film on which the surface treatment layer is formed is subjected to a demolding treatment to form a demolding layer by applying a release agent or the like, and a surface treatment film having a surface treatment layer formed on the demolding layer is prepared. Then, after the surface treatment film is laminated on the liquid crystal polarizer, the laminate of the liquid crystal polarizer and the first liquid crystal phase difference layer, or the laminate of the liquid crystal polarizer and the first liquid crystal phase difference layer and the second liquid crystal phase difference layer, the resin film is peeled off. Thus, as a protective layer, an optical laminate that does not include a resin film but includes a surface treatment layer can be obtained.

[0106] Examples of the surface treatment layer include a hard coating layer, an anti-glare layer, an anti-reflection layer, an antistatic layer, an anti-fouling layer, an anti-blocking layer, etc. The surface treatment layer can be formed on the surface of a resin film by coating or a release layer formed on the resin film, and can be formed by modifying the surface of the resin film when the protective layer includes a resin film.

[0107] The method for forming the surface treatment layer is not particularly limited, and a known method can be used. The surface treatment layer may be formed on one surface or both surfaces of the resin film.

[0108] The hard coating layer has the function of increasing the surface hardness of the protective layer and is provided for the purpose of preventing scratches on the surface. By forming a hard coating layer on a resin film, the hardness and scratch resistance of the protective layer can be increased. The hard coating layer preferably shows a value of H or harder than H in the pencil hardness test (measured by placing an optical film having a hard coating layer on a glass plate) specified in JIS K 5600-5-4:1999 "General Test Methods for Coatings - Part 5: Mechanical Properties of Coatings - Section 4: Scratch Hardness (Pencil Method)".

[0109] The hard coat layer may contain various fillers as required for the purpose of adjusting the refractive index, improving the bending elastic modulus, stabilizing the volume shrinkage, and improving heat resistance, antistatic properties, antiglare properties, etc. In addition, the hard coat layer may also contain additives such as antioxidants, ultraviolet absorbers, light stabilizers, antistatic agents, leveling agents, and defoaming agents.

[0110] (Outer coating)

[0111] The polarizing plate may have an outer coating (second protective layer) covering the surface of the first liquid crystal phase difference layer side of the liquid crystal polarizer. The outer coating can be formed by applying a material (composition) constituting the outer coating such as a photocurable resin or a water-soluble polymer on the surface of the liquid crystal polarizer and drying or curing it. As a photocurable resin, for example, (meth) acrylic resins, urethane resins, (meth) acrylic urethane resins, epoxy resins, silicone resins, etc. can be cited. As a water-soluble polymer, for example, poly (meth) acrylamide polymers; polyvinyl alcohol and ethylene-vinyl alcohol copolymers, ethylene-vinyl acetate copolymers, (meth) acrylic acid or its anhydride-vinyl alcohol copolymers and other vinyl alcohol polymers; carboxyvinyl polymers; polyvinyl pyrrolidone; starch; sodium alginate; polyethylene oxide polymers, etc. can be cited.

[0112] The thickness of the outer coating is usually 0.1 μm or more and 10.0 μm or less, preferably 5.0 μm or less, and more preferably 3.0 μm or less. If the thickness of the outer coating is 10 μm or more, the uneven reflection color tone of the bent portion is easily noticeable in the bend test, and if it is less than 0.1 μm, the function of preventing the pigment from diffusing is easily impaired in a high temperature environment.

[0113] (First liquid crystal phase difference layer and second liquid crystal phase difference layer)

[0114] The first liquid crystal phase difference layer and the second liquid crystal phase difference layer are films that show a phase difference in the plane or thickness direction, and are layers (cured layers) of polymers containing polymerizable liquid crystal compounds, or films consisting of two layers of the layer and an orientation film. The first liquid crystal phase difference layer and the second liquid crystal phase difference layer include a cured layer of a second liquid crystal composition containing a polymerizable liquid crystal compound. The first liquid crystal phase difference layer and / or the second liquid crystal phase difference layer may each include a second orientation film. The second liquid crystal composition used to form the first liquid crystal phase difference layer 21 and the second liquid crystal composition used to form the second liquid crystal phase difference layer 22 may be the same as or different from each other.

[0115] The first liquid crystal phase difference layer and the second liquid crystal phase difference layer are usually formed by coating the second liquid crystal composition on the second orientation film formed on the second substrate layer, and polymerizing the polymerizable liquid crystal compound contained in the second liquid crystal composition. The first liquid crystal phase difference layer and the second liquid crystal phase difference layer usually include a layer obtained by curing the polymerizable liquid crystal compound in an oriented state. In order to produce a phase difference in the plane, it is necessary to be a cured layer obtained by polymerizing the polymerizable groups of the polymerizable liquid crystal compound in a state where the polymerizable liquid crystal compound is oriented in a horizontal direction relative to the second substrate layer. At this time, when the polymerizable liquid crystal compound is a rod-shaped liquid crystal compound, the liquid crystal phase difference layer can be set to a positive A plate, and when the polymerizable liquid crystal compound is a disc-shaped liquid crystal compound, the liquid crystal phase difference layer can be set to a negative A plate.

[0116] In order to highly realize the anti-reflection function of the optical stack, the combination of the first liquid crystal phase difference layer and the second liquid crystal phase difference layer only needs to have the λ / 4 plate function (i.e., the phase difference function of π / 2) in the entire range of visible light. In addition, the first liquid crystal phase difference layer or the second liquid crystal phase difference layer contained in the optical stack is preferably a reverse wavelength dispersion λ / 4 layer. As the first liquid crystal phase difference layer and the second liquid crystal phase difference layer, it is also preferred to combine two or more liquid crystal phase difference layers with different orientations. As a combination of two or more liquid crystal phase difference layers, for example, a liquid crystal phase difference layer having a λ / 2 plate function (i.e., a phase difference function of π) with positive wavelength dispersion (hereinafter also referred to as a "λ / 2 layer") and a liquid crystal phase difference layer having a λ / 4 plate function (i.e., a phase difference function of π / 2) with positive wavelength dispersion (hereinafter also referred to as a "λ / 4 layer") . Alternatively, from the viewpoint of being able to compensate for the anti-reflection function in the oblique direction, one of the first liquid crystal phase difference layer and the second liquid crystal phase difference layer may be a layer having anisotropy in the thickness direction (positive C plate), and the other may be a reverse wavelength dispersion λ / 4 layer. In addition, the first liquid crystal phase difference layer and the second liquid crystal phase difference layer may each form an oblique orientation state or a cholesteric orientation state.

[0117] When the combination of the first liquid crystal phase difference layer and the second liquid crystal phase difference layer is adjusted to have the function of a λ / 4 plate in the entire visible light range, the phase difference body including the first liquid crystal phase difference layer and the second liquid crystal phase difference layer preferably has an in-plane phase difference for light of wavelength λ [nm], that is, Re (λ) that satisfies the optical properties shown in the following formula (1), and preferably satisfies the optical properties shown in the following formulas (2) and (3). The phase difference body is a laminated film on which a plurality of phase difference plates are stacked, and is a laminated film that exhibits a phase difference in the in-plane or thickness direction based on the stacked plurality of phase difference plates. The phase difference plate is a film including the first liquid crystal phase difference layer or the second liquid crystal phase difference layer, and is a film that exhibits an optical function as the first liquid crystal phase difference layer or the second liquid crystal phase difference layer.

[0118] 100nm<Re(550)<160nm (1)

[0119] Re(450) / Re(550)≤1.0 (2)

[0120] 1.00≤Re(650) / Re(550) (3)

[0121] [In formulas (1) to (3),

[0122] Re(450) represents the in-plane phase difference value of the phase difference body for light with a wavelength of 450 nm.

[0123] Re(550) represents the in-plane phase difference value of the phase difference body for light with a wavelength of 550 nm.

[0124] Re(650) represents the in-plane phase difference value of the phase difference body for light with a wavelength of 650 nm.

[0125] If "Re (450) / Re (550)" in the above formula (2) is greater than 1.0, the light leakage on the short wavelength side of the optical laminate having the phase difference body becomes larger. "Re (450) / Re (550)" is preferably 0.7 or more and 1.0 or less, more preferably 0.80 or more and 0.95 or less, further preferably 0.80 or more and 0.92 or less, and particularly preferably 0.82 or more and 0.88 or less. The value of "Re (450) / Re (550)" can be arbitrarily adjusted by adjusting the mixing ratio of the polymerizable liquid crystal compound in the second liquid crystal composition, the stacking angle of the first liquid crystal phase difference layer and the second liquid crystal phase difference layer, and their phase difference values.

[0126] The in-plane phase difference values ​​of the first liquid crystal phase difference layer and the second liquid crystal phase difference layer can be adjusted by the thickness of the two liquid crystal phase difference layers. Since the in-plane phase difference value is determined by the following formula (4), in order to obtain the desired in-plane phase difference value (Re (λ)), it is only necessary to adjust Δn (λ) and the film thickness d. The thickness of the first liquid crystal phase difference layer and the second liquid crystal phase difference layer is preferably greater than 0.5 μm and less than 5 μm, and more preferably greater than 1 μm and less than 3 μm. The thickness of the first liquid crystal phase difference layer and the second liquid crystal phase difference layer can be measured by an interference film thickness meter, a laser microscope, or a probe film thickness meter. It should be noted that Δn (λ) depends on the molecular structure of the polymerizable liquid crystal compound described later.

[0127] Re(λ)=d×Δn(λ) (4)

[0128] [In formula (4),

[0129] Re(λ) represents the in-plane phase difference value of the liquid crystal phase difference layer at wavelength λ [nm],

[0130] d represents the thickness of the liquid crystal phase difference layer,

[0131] Δn(λ) represents the birefringence at wavelength λ [nm]. ]

[0132] When using a combination of a λ / 2 layer with positive wavelength dispersion and a λ / 4 layer with positive wavelength dispersion as a phase difference body adjusted to have the function of a λ / 4 plate in the entire visible light range, it is sufficient to combine a layer having the optical properties represented by the following formulas (1), (6) and (7) with a layer having the optical properties represented by the following formulas (5) to (7) in a specific slow axis relationship.

[0133] 100nm<Re(550)<160nm (1)

[0134] 200nm<Re(550)<320nm (5)

[0135] Re(450) / Re(550)≥1.00 (6)

[0136] 1.00≥Re(650) / Re(550) (7)

[0137] [In formulas (1) and (5) to (7),

[0138] Re(450) represents the in-plane phase difference value of the phase difference body for light with a wavelength of 450 nm.

[0139] Re(550) represents the in-plane phase difference value of the phase difference body for light with a wavelength of 550 nm.

[0140] Re(650) represents the in-plane phase difference value of the phase difference body for light with a wavelength of 650 nm.

[0141] As a method of combining the λ / 2 layer with the λ / 4 layer, there can be mentioned the known methods described in Japanese Patent Publication No. 2015-163935, WO2013 / 137464, etc. From the viewpoint of viewing angle compensation, it is preferred to use a λ / 2 layer formed by a second liquid crystal composition containing a disc-shaped polymerizable liquid crystal compound and a λ / 4 layer formed by a second liquid crystal composition containing a rod-shaped polymerizable liquid crystal compound.

[0142] The positive C plate is not particularly limited as long as it is a layer having anisotropy in the thickness direction, and has the optical properties represented by the following formula (8) when it is not tilted or cholesteric oriented.

[0143] nx≈ny<nz (8)

[0144] [In formula (8),

[0145] nx represents the principal refractive index at a wavelength λ [nm] in the plane of the positive C plate.

[0146] Ny represents the refractive index of the positive C plate at a wavelength λ [nm] in a direction perpendicular to nx in the same plane as nx.

[0147] nz(λ) represents the refractive index at a wavelength λ [nm] in the thickness direction of the positive C plate.

[0148] In the case of nx≈ny, nx can be set to the refractive index in any direction within the plane of the positive C plate.]

[0149] The retardation value Rth(550) in the thickness direction of the positive C plate at a wavelength of 550nm is usually in the range of -170nm to -10nm, preferably in the range of -150nm to -20nm, and more preferably in the range of -100nm to -40nm. If the retardation value in the thickness direction is within this range, the anti-reflection property from the oblique direction can be further improved.

[0150] The positive C plate is preferably formed of a second liquid crystal composition containing a rod-shaped polymerizable liquid crystal compound.

[0151] As the first liquid crystal phase difference layer and the second liquid crystal phase difference layer, in addition to the above-mentioned structure, for the structure with tilted orientation and cholesteric orientation, as long as it is a structure that realizes the anti-reflection function, it can also be used without particular restriction. As this structure, for example, the known structures described in WO2021 / 060378, WO2021 / 132616, WO2021 / 132624, etc. can be cited.

[0152] (Second Liquid Crystal Composition)

[0153] The second liquid crystal composition is a composition for forming the first liquid crystal phase difference layer and a composition for forming the second liquid crystal phase difference layer. The second liquid crystal composition includes a polymerizable liquid crystal compound, and may further include additives such as a solvent, a leveling agent, a polymerization initiator, a sensitizer, an inhibitor, a cross-linking agent, a bonding agent, and a reactive additive. From the viewpoint of processability, the second liquid crystal composition preferably includes a solvent and a leveling agent. As additives, the additives described in the first liquid crystal composition can be cited, and the content of the additives in the second liquid crystal composition, etc., can also be set to the content of the range described in the first liquid crystal composition.

[0154] The polymerizable liquid crystal compound contained in the second liquid crystal composition refers to a liquid crystal compound having at least one polymerizable group, particularly a photopolymerizable group, in the molecule. As the polymerizable liquid crystal compound, for example, a polymerizable liquid crystal compound previously known in the field of phase difference film can be used. Liquid crystal can be a thermotropic liquid crystal or a lyotropic liquid crystal, but from the perspective of being able to perform precise film thickness control, a thermotropic liquid crystal is preferred. As a phase-ordered structure of a thermotropic liquid crystal, it can be a nematic liquid crystal or a smectic liquid crystal. It can be a rod-shaped liquid crystal or a disc-shaped liquid crystal. The polymerizable liquid crystal compound can be used alone or in combination of two or more.

[0155] As a polymerizable liquid crystal compound for obtaining a λ / 4 layer with reverse wavelength dispersion, from the viewpoint of exhibiting reverse wavelength dispersion, a liquid crystal having a T-type or H-type mesomorphic structure which further has birefringence in a direction perpendicular to the molecular long axis direction is preferred. From the viewpoint of obtaining stronger dispersion, a T-type liquid crystal is more preferred. Specifically, as the structure of the T-type liquid crystal, for example, a compound represented by the following formula (I) can be cited.

[0156] [Chemical formula 1]

[0157]

[0158] [In formula (I),

[0159] Ar represents a divalent aromatic group which may have a substituent. Preferably, the divalent aromatic group contains at least one of a nitrogen atom, an oxygen atom, and a sulfur atom. When the divalent group Ar contains two or more aromatic groups, the two or more aromatic groups may be bonded to each other by a divalent connecting group such as a single bond, -CO-O-, or -O-.

[0160] G 1 and G 2 Each independently represents a divalent aromatic group or a divalent alicyclic hydrocarbon group. Here, the hydrogen atoms contained in the divalent aromatic group or the divalent alicyclic hydrocarbon group may be substituted by a halogen atom, an alkyl group having 1 to 4 carbon atoms, a fluoroalkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a cyano group or a nitro group, and the carbon atoms constituting the divalent aromatic group or the divalent alicyclic hydrocarbon group may be replaced by an oxygen atom, a sulfur atom or a nitrogen atom.

[0161] L 1 , L 2 , B 1 and B 2 Each is independently a single bond or a divalent linking group.

[0162] k and l each independently represent an integer from 0 to 3, and satisfy the relationship 1≤k+1. Here, when 2≤k+1, B 1 and B 2 , G 1 and G 2 They may be the same as or different from each other.

[0163] E 1 and E 2 Each independently represents an alkanediyl group having 1 to 17 carbon atoms, wherein the hydrogen atoms contained in the alkanediyl group may be substituted by halogen atoms, and the -CH2- contained in the alkanediyl group may be substituted by -O-, -S-, or -COO-. When there are multiple -O-, -S-, or -COO- groups, they are not adjacent to each other.

[0164] P 1 and P 2 Each independently represents a polymerizable group or a hydrogen atom, and at least one of them is a polymerizable group.]

[0165] G 1 and G 2 Each independently preferably is a 1,4-phenylenediyl group which may be substituted with at least one substituent selected from a halogen atom and an alkyl group having 1 to 4 carbon atoms, or a 1,4-cyclohexanediyl group which may be substituted with at least one substituent selected from a halogen atom and an alkyl group having 1 to 4 carbon atoms; more preferably is a 1,4-phenylenediyl group substituted with a methyl group, an unsubstituted 1,4-phenylenediyl group, or an unsubstituted 1,4-trans-cyclohexanediyl group; and particularly preferably is an unsubstituted 1,4-phenylenediyl group or an unsubstituted 1,4-trans-cyclohexanediyl group.

[0166] In addition, it is preferred that there are a plurality of G 1 and G 2 At least one of them is a divalent alicyclic hydrocarbon group, and more preferably 1 or L 2 Bonded G 1 and G 2 At least one of them is a divalent alicyclic hydrocarbon group.

[0167] L 1 and L 2 Each of them is independently preferably a single bond, an alkylene group having 1 to 4 carbon atoms, -O-, -S-, -R a1 OR a2 -、-R a3 COOR a4 -、-R a5 OCOR a6 -、R a7 OC=OOR a8 -、-N=N-、-CRc =CR d -, or C≡C-. Here, R a1 ~R a8 Each independently represents a single bond or an alkylene group having 1 to 4 carbon atoms, and R c and R d represents an alkyl group having 1 to 4 carbon atoms or a hydrogen atom. 1 and L 2 Each independently is more preferably a single bond, -O Ra2-1 -、-CH2-、-CH2CH2-、-COOR a4-1 -, or OCOR a6-1 -. Here, R a2-1 , R a4-1 , R a6-1 Each independently represents a single bond, -CH2-, or -CH2CH2-. 1 and L 2 Each independently is further preferably a single bond, -O-, -CH2CH2-, -COO-, -COOCH2CH2-, or OCO-.

[0168] B 1 and B 2 Each of them is independently preferably a single bond, an alkylene group having 1 to 4 carbon atoms, -O-, -S-, -R a9 OR a10 -、-R a11 COOR a12 -、-R a13 OCOR a14 -, or R a15 OC=OOR a16 -. Here, R a9 ~R a16 Each independently represents a single bond or an alkylene group having 1 to 4 carbon atoms. 1 and B 2 Each independently is more preferably a single bond, -OR a10-1 -、-CH2-、-CH2CH2-、-COOR a12 -1 -, or OCOR a14-1 -. Here, R a10-1 , R a12-1 , R a14-1 Each independently represents a single bond, -CH2-, or -CH2CH2-. 1 and B 2 Each independently is further preferably a single bond, -O-, -CH2CH2-, -COO-, -COOCH2CH2-, -OCO-, or OCOCH2CH2-.

[0169] From the viewpoint of achieving reverse wavelength dispersion, k and l are preferably in the range of 2≤k+l≤6, preferably k+l=4, and more preferably k=2 and l=2. If k=2 and l=2, a symmetrical structure is formed, which is preferred.

[0170] Preferred E 1 and E 2 Each independently is an alkanediyl group having 1 to 17 carbon atoms, and more preferably an alkanediyl group having 4 to 12 carbon atoms.

[0171] As P 1 or P 2 The polymerizable group represented by , includes epoxy, vinyl, vinyloxy, 1-chlorovinyl, isopropenyl, 4-vinylphenyl, acryloyloxy, methacryloyloxy, oxirane and oxetanyl, etc. Among them, acryloyloxy, methacryloyloxy, vinyloxy, oxirane and oxetanyl are preferred, and acryloyloxy is more preferred.

[0172] Ar preferably has at least one selected from an aromatic hydrocarbon ring that may have a substituent, an aromatic heterocycle that may have a substituent, and an electron-withdrawing group. As the aromatic hydrocarbon ring, for example, a benzene ring, a naphthalene ring, an anthracene ring, etc. can be cited, preferably a benzene ring, a naphthalene ring. As the aromatic heterocycle, a furan ring, a benzofuran ring, a pyrrole ring, an indole ring, a thiophene ring, a benzothiophene ring, a pyridine ring, a pyrazine ring, a pyrimidine ring, a triazole ring, a triazine ring, a pyrroline ring, an imidazole ring, a pyrazole ring, a thiazole ring, a benzothiazole ring, a thienothiazole ring, an oxazole ring, a benzoxazole ring, and a phenanthroline ring, etc. can be cited. Among them, preferably there is a thiazole ring, a benzothiazole ring, or a benzofuran ring, more preferably there is a benzothiazolyl. In addition, when Ar contains a nitrogen atom, it is preferred that the nitrogen atom has π electrons.

[0173] In formula (I), the total number Nπ of π electrons contained in the divalent aromatic group represented by Ar is preferably 8 or more, more preferably 10 or more, further preferably 14 or more, and particularly preferably 16 or more. It is preferably 30 or less, more preferably 26 or less, and further preferably 24 or less.

[0174] As the aromatic group represented by Ar, for example, the following groups can be preferably mentioned.

[0175] [Chemical formula 2]

[0176]

[0177] [In formula (Ar-1) to formula (Ar-23),

[0178] The mark indicates the connection part.

[0179] Z0 , Z 1 and Z 2 Each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 12 carbon atoms, a cyano group, a nitro group, an alkylsulfinyl group having 1 to 12 carbon atoms, an alkylsulfonyl group having 1 to 12 carbon atoms, a carboxyl group, a fluoroalkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, an alkylthio group having 1 to 12 carbon atoms, an N-alkylamino group having 1 to 12 carbon atoms, an N,N-dialkylamino group having 2 to 12 carbon atoms, an N-alkylsulfamoyl group having 1 to 12 carbon atoms, or an N,N-dialkylsulfamoyl group having 2 to 12 carbon atoms.

[0180] Q 1 and Q 2 Each independently represents -CR 2’ R 3’ -、-S-、-NH-、-NR 2’ -, -CO- or O-, R 2’ and R 3’ Each independently represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.

[0181] J 1 and J 2 Each independently represents a carbon atom or a nitrogen atom.

[0182] Y 1 , Y 2 and Y 3 Each independently represents an aromatic hydrocarbon group or an aromatic heterocyclic group which may be substituted.

[0183] W 1 and W 2 Each independently represents a hydrogen atom, a cyano group, a methyl group or a halogen atom.

[0184] m represents an integer from 0 to 6.]

[0185] As Y 1 , Y 2 and Y 3 The aromatic hydrocarbon group in the group includes aromatic hydrocarbon groups having 6 to 20 carbon atoms, such as phenyl, naphthyl, anthracenyl, phenanthrenyl, and biphenyl, preferably phenyl and naphthyl, and more preferably phenyl. The aromatic heterocyclic group includes aromatic heterocyclic groups having 4 to 20 carbon atoms, such as furanyl, pyrrolyl, thienyl, pyridyl, thiazolyl, and benzothiazolyl, which contain at least one hetero atom such as a nitrogen atom, an oxygen atom, or a sulfur atom, preferably furanyl, thienyl, pyridyl, thiazolyl, and benzothiazolyl.

[0186] Y 1 , Y 2 and Y 3Each independently may be a polycyclic aromatic hydrocarbon group or a polycyclic aromatic heterocyclic group which may be substituted. The polycyclic aromatic hydrocarbon group refers to a condensed polycyclic aromatic hydrocarbon group or a group derived from a collection of aromatic rings. The polycyclic aromatic heterocyclic group refers to a condensed polycyclic aromatic heterocyclic group or a group derived from a collection of aromatic rings.

[0187] Z 0 , Z 1 and Z 2 Each of Z is independently preferably a hydrogen atom, a halogen atom, an alkyl group having 1 to 12 carbon atoms, a cyano group, a nitro group, or an alkoxy group having 1 to 12 carbon atoms. 0 More preferably, Z is a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a cyano group. 1 and Z 2 More preferred are a hydrogen atom, a fluorine atom, a chlorine atom, a methyl group and a cyano group.

[0188] Q 1 and Q 2 Preferred are -NH-, -S-, -NR 2’ -、-O-,R 2’ A hydrogen atom is preferred, and -S-, -O-, and -NH- are particularly preferred.

[0189] Among the compounds represented by formulae (Ar-1) to (Ar-23), compounds represented by formulae (Ar-6) and (Ar-7) are preferred from the viewpoint of molecular stability.

[0190] In the compounds represented by formulas (Ar-16) to (Ar-23), Y 1 The nitrogen atom and Z to which it can be bonded 0 Together, they form an aromatic heterocyclic group. Examples of the aromatic heterocyclic group include the aromatic heterocyclic groups described above as the aromatic heterocyclic rings that Ar may have, such as a pyrrole ring, an imidazole ring, a pyrroline ring, a pyridine ring, a pyrazine ring, a pyrimidine ring, an indole ring, a quinoline ring, an isoquinoline ring, a purine ring, and a pyrrolidine ring. The aromatic heterocyclic group may have a substituent. In addition, Y 1 The nitrogen atom and Z to which it can be bonded 0 Together, they represent the aforementioned optionally substituted polycyclic aromatic hydrocarbon group or polycyclic aromatic heterocyclic group, for example, a benzofuran ring, a benzothiazole ring, a benzoxazole ring, and the like.

[0191] Among polymerizable liquid crystal compounds, compounds with a maximum absorption wavelength of 300 to 400 nm are preferred. It is advantageous in terms of the long-term stability of the second liquid crystal composition, and the orientation and uniformity of the film thickness of the cured layer of the second liquid crystal composition contained in the first liquid crystal phase difference layer and the second liquid crystal phase difference layer can be improved. It should be noted that the maximum absorption wavelength of the polymerizable liquid crystal compound can be measured using an ultraviolet-visible spectrophotometer in a solvent. The solvent is a solvent that can dissolve the polymerizable liquid crystal compound, for example, chloroform and the like can be cited.

[0192] Examples of the disc-shaped polymerizable liquid crystal compound include a compound containing a group represented by formula (W) (hereinafter also referred to as “polymerizable liquid crystal compound (W)”).

[0193] [Chemical formula 3]

[0194]

[0195] [In formula (W), R 40 The following formulas (W-1) to (W-5) are represented.]

[0196] [Chemical formula 4]

[0197]

[0198] [In formulas (W-1) to (W-5),

[0199] X 40 and Z 40 Each independently represents an alkanediyl group having 1 to 12 carbon atoms, wherein the hydrogen atoms contained in the alkanediyl group may be substituted by an alkoxy group having 1 to 5 carbon atoms, and the hydrogen atoms contained in the alkoxy group may be substituted by a halogen atom. In addition, -CH2- constituting the alkanediyl group may be replaced by -O- or -CO-.

[0200] m2 represents an integer.]

[0201] Examples of the rod-shaped polymerizable liquid crystal compound include compounds represented by formula (II), formula (III), formula (IV), formula (V), formula (VI), or formula (VII).

[0202] P11-B11-E11-B12-A11-B13-A12-B14-A13-B15-A14-B16-E12-B17-P12 (II)

[0203] P11-B11-E11-B12-A11-B13-A12-B14-A13-B15-A14-F11 (III)

[0204] P11-B11-E11-B12-A11-B13-A12-B14-A13-B15-E12-B17-P12 (IV)

[0205] P11-B11-E11-B12-A11-B13-A12-B14-A13-F11 (V)

[0206] P11-B11-E11-B12-A11-B13-A12-B14-E12-B17-P12 (VI)

[0207] P11-B11-E11-B12-A11-B13-A12-F11 (VII)

[0208] [In formulas (II) to (VII),

[0209] A11 to A14 each independently represent a divalent alicyclic hydrocarbon group or a divalent aromatic hydrocarbon group. The hydrogen atoms contained in the divalent alicyclic hydrocarbon group and the divalent aromatic hydrocarbon group may be substituted by a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, a cyano group or a nitro group, and the hydrogen atoms contained in the alkyl group having 1 to 6 carbon atoms and the alkoxy group having 1 to 6 carbon atoms may be substituted by a fluorine atom.

[0210] B11 and B17 each independently represent -O-, -S-, -CO-O-, -O-CO-, -O-CO-O-, -CO-NR 16 -、-NR 16 -CO-, -CO-, -CS-, or a single bond. 16 It represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms.

[0211] B12 to B16 each independently represent -C≡C-, -CH=CH-, -CH2-CH2-, -O-, -S-, -C(=O)-, -C(=O)-O-, -OC(=O)-, -OC(=O)-O-, -CH=N-, -N=CH-, -N=N-, -C(=O)-NR 16 -、-NR 16 -C(=O)-, -OCH2-, -OCF2-, -CH2O-, -CF2O-, -CH=CH-C(=O)-O-, -OC(=O)-CH=CH- or a single bond.

[0212] E11 and E12 each independently represent an alkanediyl group having 1 to 12 carbon atoms, wherein the hydrogen atoms contained in the alkanediyl group may be substituted by an alkoxy group having 1 to 5 carbon atoms, and the hydrogen atoms contained in the alkoxy group may be substituted by a halogen atom. In addition, -CH2- constituting the alkanediyl group may be replaced by -O- or -CO-.

[0213] F11 represents a hydrogen atom, an alkyl group having 1 to 13 carbon atoms, an alkoxy group having 1 to 13 carbon atoms, a cyano group, a nitro group, a trifluoromethyl group, a dimethylamino group, a hydroxyl group, a hydroxymethyl group, a formyl group, a sulfo group (-SO3H), a carboxyl group, an alkoxycarbonyl group having 1 to 10 carbon atoms, or a halogen atom, and the -CH2- constituting the alkyl group and the alkoxy group may be replaced by -O-.

[0214] P11 and P12 each independently represent a polymerizable group.]

[0215] The content of the polymerizable liquid crystal compound in the second liquid crystal composition is, for example, 70 to 99.5 parts by mass, preferably 80 to 99 parts by mass, relative to 100 parts by mass of the solid content of the second liquid crystal composition. If the content of the polymerizable liquid crystal compound is within the above range, it is advantageous from the perspective of the orientation of the resulting cured layer (liquid crystal cured film). It should be noted that in this specification, the so-called solid content of the second liquid crystal composition refers to all components after removing volatile components such as organic solvents from the second liquid crystal composition.

[0216] (1st base material layer, 2nd base material layer)

[0217] As the first substrate layer coated with the first liquid crystal composition and the second substrate layer coated with the second liquid crystal composition, a glass substrate and a film substrate can be cited, preferably a film substrate, and from the aspect of being able to continuously manufacture a liquid crystal polarizer, a first liquid crystal phase difference layer and a second liquid crystal phase difference layer, a long roll film is more preferred. The first liquid crystal composition and the second liquid crystal composition can be coated on the alignment films formed on the first substrate layer and the second substrate layer, respectively.

[0218] Examples of the resin constituting the film substrate include olefin resins such as polyethylene and polypropylene; cyclic olefin resins having a ring system or a norbornene structure; polyvinyl alcohol; polyester resins such as polyethylene terephthalate and polyethylene naphthalate; poly(meth)acrylic resins; cellulose ester resins such as triacetyl cellulose, diacetyl cellulose and cellulose acetate propionate; polyimide resins; polycarbonate; polysulfone; polyether sulfone; polyether ketone; polyphenylene sulfide; polyphenylene ether, etc.

[0219] A commercially available cellulose ester resin substrate can be used as the film substrate. Examples of such cellulose ester resin substrates include "FUJITAC Film" (manufactured by Fujifilm Corporation); "KC8UX2M", "KC8UY" and "KC4UY" (manufactured by Konica Minolta Opto Co., Ltd.).

[0220] Commercially available cyclic olefin resins can be used as the cyclic olefin resin constituting the film substrate. Examples of such cyclic olefin resins include "Topas" (registered trademark) (manufactured by Ticona (Germany)), "Arton" (registered trademark) (manufactured by JSR Corporation), "ZEONOR" (registered trademark), "ZEONEX" (registered trademark) (manufactured by ZEON Corporation of Japan), and "APEL" (registered trademark) (manufactured by Mitsui Chemicals, Inc.).

[0221] When the first substrate layer is used as a protective layer in its entirety or in part, the first substrate layer preferably has the material and layer structure described in the above-mentioned protective layer. When a part of the first substrate layer is used as a protective layer, for example, as long as a release layer is formed on the surface of the film substrate and a liquid crystal polarizer is formed on the film substrate, the film substrate can be peeled off and removed.

[0222] From the aspect of quality that can be operated practically, it is preferred that the first substrate layer and the second substrate layer are thin, but if they are too thin, the strength is reduced and there is a tendency for poor processability. From this viewpoint, the thickness of the first substrate layer and the second substrate layer is usually 5 μm to 300 μm, preferably 10 μm to 200 μm, and more preferably 10 to 50 μm. By peeling off the first substrate layer and then transferring the liquid crystal polarizer (the cured layer of the first liquid crystal composition), peeling off the second substrate layer and then transferring the first liquid crystal phase difference layer and the second liquid crystal phase difference layer, the thin film of the optical laminate can be sought.

[0223] (1st orientation film, 2nd orientation film)

[0224] The first alignment film and the second alignment film have an alignment regulating force for aligning the polymerizable liquid crystal compound in a desired direction.

[0225] The first orientation film and the second orientation film make it easy to orient the liquid crystal of the polymerizable liquid crystal compound. The state of liquid crystal orientation such as horizontal orientation, vertical orientation, mixed orientation, and tilted orientation varies according to the properties of the first orientation film and the second orientation film, as well as the polymerizable liquid crystal compound, and its combination can be selected arbitrarily. For example, if the first orientation film and / or the second orientation film is a material that reflects horizontal orientation as an orientation limiting force, the polymerizable liquid crystal compound can form a horizontal orientation or a mixed orientation, and if it is a material that reflects a vertical orientation, the polymerizable liquid crystal compound can form a vertical orientation or a tilted orientation. Expressions such as horizontal and vertical indicate the direction of the long axis of the polymerizable liquid crystal compound that is oriented when the plane of the liquid crystal polarizer and the first liquid crystal phase difference layer and the second liquid crystal phase difference layer is used as a reference. For example, the so-called vertical orientation is a long axis of a polymerizable liquid crystal compound oriented in a direction perpendicular to the plane of the liquid crystal polarizer, the first liquid crystal phase difference layer or the second liquid crystal phase difference layer. The so-called vertical mentioned here refers to 90°±20° relative to the plane of the liquid crystal polarizer, the first liquid crystal phase difference layer or the second liquid crystal phase difference layer.

[0226] The orientation restraining force can be arbitrarily adjusted by using the surface state and friction conditions when the orientation film is formed of an orientation polymer, and can be arbitrarily adjusted by using polarized light irradiation conditions, etc. when the orientation film is formed of a photo-orientation polymer. In addition, the liquid crystal orientation can also be controlled by selecting the surface tension, liquid crystal properties, etc. of the polymerizable liquid crystal compound.

[0227] In the case where the first orientation film and the second orientation film are formed between a film substrate or a glass substrate and a cured product layer of the first liquid crystal composition or the second liquid crystal composition, it is preferably insoluble in the solvent contained in the first liquid crystal composition or the second liquid crystal composition, and preferably has heat resistance in the heating treatment for removing the solvent and orienting the polymerizable liquid crystal compound. As the first orientation film and the second orientation film, an orientation film containing an oriented polymer, a photo-orientation film and a groove orientation film, a stretched film stretched along the orientation direction, etc. can be cited independently. When applied to a long roll film, a photo-orientation film is preferred from the aspect of being able to easily control the orientation direction.

[0228] The thickness of the first alignment film and the second alignment film are each independently in the range of usually 10 nm to 5000 nm, preferably 10 nm to 1000 nm, and more preferably 30 to 300 nm.

[0229] As the oriented polymer used in the rubbing oriented film, polyamides, gelatins, polyimides with amide bonds in the molecule and polyamic acid, polyvinyl alcohol, alkyl-modified polyvinyl alcohol, polyacrylamide, polyoxazole, polyethyleneimine, polystyrene, polyvinyl pyrrolidone, polyacrylic acid and polyacrylates etc. as their hydrolyzates can be enumerated. Among them, polyvinyl alcohol is preferred. These oriented polymers can be used alone or in combination of two or more.

[0230] As a method of rubbing, there can be mentioned a method of bringing an oriented polymer film formed on the surface of a film substrate or a glass substrate by applying an oriented polymer composition to a substrate and annealing the oriented polymer film into contact with a rotating rubbing roller wound with a rubbing cloth.

[0231] The photo-alignment film comprises a polymer, oligomer or monomer having a photoreactive group. The photo-alignment film can obtain an orientation restriction force by irradiating polarized light. By selecting the polarization direction of the irradiated polarized light, the direction of the orientation restriction force can be arbitrarily controlled. From this point of view, the photo-alignment film is more preferred.

[0232] The so-called photoreactive group refers to a group that generates liquid crystal orientation ability by irradiation with light. Specifically, it is a group that generates photoreactions such as orientation induction or isomerization reaction, dimerization reaction, photocrosslinking reaction, or photodecomposition reaction of molecules generated by irradiation with light, which is the origin of liquid crystal orientation ability. Among the photoreactive groups, from the perspective of excellent orientation, groups that undergo dimerization reaction or photocrosslinking reaction are preferred. As a photoreactive group capable of the above-mentioned reaction, a group having an unsaturated bond, especially a double bond, is preferred, and a group having at least one selected from a carbon-carbon double bond (C=C bond), a carbon-nitrogen double bond (C=N bond), a nitrogen-nitrogen double bond (N=N bond), and a carbon-oxygen double bond (C=O bond) is more preferred.

[0233] As photoreactive groups having C=C bonds, for example, vinyl, polyene, stilbene, stilbazolyl, stilbazolinium, chalcone and cinnamoyl groups can be cited. From the perspective of easy control of reactivity and the orientation restriction force during photo-orientation, chalcone and cinnamoyl groups are preferred. As photoreactive groups having C=N bonds, groups having structures such as aromatic Schiff bases and aromatic hydrazones can be cited. As photoreactive groups having N=N bonds, groups with azobenzene as the basic structure, such as azobenzene, azonaphthyl, aromatic heterocyclic azo, disazo and formazan, can be cited. As photoreactive groups having C=O bonds, benzophenone, coumarin, anthraquinone and maleimide groups can be cited. These groups can have substituents such as alkyl, alkoxy, aryl, allyloxy, cyano, alkoxycarbonyl, hydroxyl, sulfonic acid and halogenated alkyl.

[0234] When irradiating polarized light, the polarized light may be irradiated directly from the film surface, or may be irradiated from the film substrate or glass substrate side, or transmitted polarized light. In addition, it is particularly preferred that the polarized light is substantially parallel light. The wavelength of the irradiated polarized light is preferably a wavelength in the wavelength region where the photoreactive group of the polymer or monomer having a photoreactive group can absorb light energy. Specifically, UV (ultraviolet light) in the range of 250 to 400 nm is particularly preferred.

[0235] (First bonding layer, adhesive layer)

[0236] The first lamination layer is a cured product layer of the active energy ray-curable composition, and is a lamination layer called a so-called adhesive layer. The adhesive layer can be formed using an adhesive composition.

[0237] As the adhesive composition, for example, there can be mentioned water-based adhesive compositions, active energy ray-curable compositions that are cured by heating or irradiation with active energy rays such as ultraviolet rays, visible light, electron beams, and X-rays, etc. As the water-based adhesive composition, for example, there can be mentioned compositions in which polyvinyl alcohol-based resins or urethane resins are dissolved in water as a main component, and compositions in which polyvinyl alcohol-based resins or urethane resins are dispersed in water as a main component. The water-based adhesive composition may further contain curing components such as polyaldehydes, melamine-based compounds, zirconium dioxide compounds, zinc compounds, glyoxal compounds, water-soluble epoxy resins, and crosslinking agents.

[0238] The adhesive composition is preferably an active energy ray-curable composition that contains a curable (polymerizable) compound as a main component and is cured by irradiation with active energy rays. Examples of the active energy ray-curable composition include a cationically polymerizable adhesive composition containing a cationically polymerizable compound as a curable compound, a radically polymerizable adhesive composition containing a radically polymerizable compound as a curable compound, and a hybrid adhesive composition containing both a cationically polymerizable compound and a radically polymerizable compound as curable compounds.

[0239] The cationically polymerizable compound is a compound or oligomer that undergoes a cation polymerization reaction and cures by irradiation with active energy rays such as ultraviolet rays, visible light, electron beams, and X-rays, or heating, and specific examples thereof include epoxy compounds, oxetane compounds, and vinyl compounds.

[0240] Examples of the epoxy compound include alicyclic epoxy compounds (compounds having one or more epoxy groups bonded to an alicyclic ring in the molecule) such as 3,4-epoxycyclohexanecarboxylic acid 3,4-epoxycyclohexylmethyl ester; aromatic epoxy compounds (compounds having an aromatic ring and an epoxy group in the molecule) such as diglycidyl ether of bisphenol A; and aliphatic epoxy compounds (compounds having at least one oxirane ring bonded to an aliphatic carbon atom in the molecule) such as 2-ethylhexyl glycidyl ether and 1,4-butanediol diglycidyl ether.

[0241] Examples of the oxetane compound include compounds having one or more oxetane rings in the molecule, such as 3-ethyl-3-{[(3-ethyloxetane-3-yl)methoxy]methyl}oxetane.

[0242] The cationic polymerizable adhesive composition preferably contains a cationic polymerization initiator. The cationic polymerization initiator may be a thermal cationic polymerization initiator or a photocationic polymerization initiator. Examples of cationic polymerization initiators include aromatic diazonium salts such as phenyldiazonium hexafluoroantimonate; aromatic iodonium salts such as diphenyliodonium tetrakis(pentafluorophenyl)borate; aromatic sulfonium salts such as triphenylsulfonium hexafluorophosphate; iron-arene complexes such as ditoluene-cyclopentadienyl iron (II) hexafluoroantimonate, etc. The content of the cationic polymerization initiator is generally 0.1 to 10 parts by mass relative to 100 parts by mass of the cationic polymerizable compound. Two or more cationic polymerization initiators may be included.

[0243] Examples of the cationically polymerizable adhesive composition include cationically polymerizable compositions described in JP-A-2016-126345 and JP-A-2021-113969.

[0244] The radical polymerizable compound is a compound or oligomer that undergoes a radical polymerization reaction and cures by irradiation with active energy rays such as ultraviolet rays, visible light, electron beams, and X-rays, or heating, and specifically includes compounds having an ethylenically unsaturated bond. Examples of the compound having an ethylenically unsaturated bond include (meth)acrylic compounds having one or more (meth)acryloyl groups in the molecule, and vinyl compounds having one or more vinyl groups in the molecule.

[0245] Examples of the (meth)acrylic compound include (meth)acrylic acid ester monomers having at least one (meth)acryloyloxy group in the molecule, (meth)acrylamide monomers, and (meth)acrylic acid oligomers having at least two (meth)acryloyl groups in the molecule obtained by reacting two or more compounds containing a functional group.

[0246] The radical polymerizable adhesive composition preferably contains a radical polymerization initiator. The radical polymerization initiator may be a thermal radical polymerization initiator or a photoradical polymerization initiator. As the radical polymerization initiator, acetophenone-based initiators such as acetophenone and 3-methylacetophenone; benzophenone-based initiators such as benzophenone, 4-chlorobenzophenone, and 4,4'-diaminobenzophenone; benzoin ether-based initiators such as benzoin propyl ether and benzoin ethyl ether; thioxanthone-based initiators such as 4-isopropylthioxanthone; xanthone, fluorenone, etc. The content of the radical polymerization initiator is usually 0.1 to 10 parts by mass relative to 100 parts by mass of the radical polymerizable compound. Two or more radical polymerization initiators may be included.

[0247] Examples of the radically polymerizable adhesive composition include radically polymerizable compositions described in JP-A-2016-126345, JP-A-2016-153474, and International Publication No. 2017 / 183335.

[0248] The active energy ray-curable adhesive composition may contain additives such as ion trapping agents, antioxidants, chain transfer agents, tackifiers, thermoplastic resins, fillers, flow regulators, plasticizers, defoamers, antistatic agents, leveling agents, and solvents as necessary.

[0249] This can be done by applying an adhesive composition on the bonding surface of at least one of the two layers bonded by the first bonding layer or the adhesive layer, overlapping the two layers via the coating layer of the adhesive composition, bonding them by pressing from top and bottom using a bonding roller, and then drying the coating layer, irradiating the coating layer with active energy rays to cure it, or heating it to cure it.

[0250] Before forming the coating layer of the adhesive composition, at least one of the bonding surfaces of the two layers may be subjected to an adhesion-facilitating treatment such as saponification treatment, corona treatment, plasma treatment, primer treatment, anchor coating treatment, or the like.

[0251] When forming the coating layer of the adhesive composition, various coating methods such as a die coater, a comma-type knife coater, a gravure coater, a wire bar coater, and a blade coater can be used.

[0252] The light irradiation intensity during irradiation with active energy rays is determined according to each composition of the active energy ray-curable adhesive composition and is not particularly limited, but is preferably 10 mW / cm 2 Above and 1000mW / cm 2 It should be noted that the irradiation intensity is preferably an intensity in a wavelength region effective for the activation of a photocationic polymerization initiator or a photoradical polymerization initiator. It is preferred to irradiate once or more times with such a light irradiation intensity and set the accumulated light amount to 10 mJ / cm2 More preferably, 100 mJ / cm 2 Above and 1000mJ / cm 2 the following.

[0253] The light source used for polymerizing and curing the active energy ray-curable adhesive composition is not particularly limited, and examples thereof include low-pressure mercury lamps, medium-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, xenon lamps, halogen lamps, chemical lamps, black light lamps, microwave-excited mercury lamps, and metal halide lamps.

[0254] The thickness of the adhesive layer formed from the water-based adhesive composition may be, for example, 5 μm or less, preferably 1 μm or less, more preferably 0.5 μm or less, and may be 0.01 μm or more, preferably 0.05 μm or more.

[0255] The thickness of the cured layer (adhesive layer) formed of the active energy ray-curable adhesive composition may be, for example, 10 μm or less, preferably 5 μm or less, more preferably 3 μm or less, and may be 0.1 μm or more, preferably 0.5 μm or more, more preferably 1 μm or more.

[0256] (Second lamination layer, third lamination layer)

[0257] The second laminating layer and the third laminating layer have a glass transition temperature Tg of 25° C. or less. The laminating layer having a Tg of 25° C. or less can be formed using, for example, an adhesive composition. The Tg of the laminating layer can be measured using a differential scanning calorimeter (DSC).

[0258] As the adhesive composition, any adhesive composition with excellent optical transparency known in the past can be used without particular limitation, for example, an adhesive composition having a base polymer such as a (meth) acrylic resin, a urethane resin, a silicone resin, a polyvinyl ether resin, etc. can be used. In addition, an active energy ray-curable adhesive composition, a thermosetting adhesive composition, etc. can also be used. Among them, an adhesive composition having excellent transparency, adhesion, removability, weather resistance, heat resistance, etc. and having an acrylic resin as a base polymer is suitable.

[0259] The adhesive composition may further include a crosslinking agent, a silane compound, an antistatic agent, and the like.

[0260] The (meth)acrylic resin contained in the adhesive composition is preferably a polymer (hereinafter also referred to as a "(meth)acrylate polymer") having a structural unit derived from an alkyl (meth)acrylate represented by the following formula (VIII) as a main component (for example, containing 50 parts by mass or more per 100 parts by mass of the structural unit of the (meth)acrylic resin).

[0261] [Chemical formula 5]

[0262]

[0263] [In formula (VIII),

[0264] R 10 represents a hydrogen atom or a methyl group,

[0265] R 20 It represents an alkyl group having 1 to 20 carbon atoms, the alkyl group may have any structure of linear, branched or cyclic, and the hydrogen atoms of the alkyl group may be substituted by an alkoxy group having 1 to 10 carbon atoms.]

[0266] Examples of the (meth)acrylic acid ester represented by formula (VIII) include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, isohexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-nonyl (meth)acrylate and isononyl (meth)acrylate, n-decyl (meth)acrylate, isodecyl (meth)acrylate, n-dodecyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, stearyl (meth)acrylate, and tert-butyl (meth)acrylate. Specific examples of the alkyl acrylate containing an alkoxy group include 2-methoxyethyl (meth)acrylate and ethoxymethyl (meth)acrylate. Among them, it is preferable to contain n-butyl (meth)acrylate or 2-ethylhexyl (meth)acrylate, and it is particularly preferable to contain n-butyl (meth)acrylate.

[0267] The (meth)acrylate polymer may contain structural units derived from other monomers in addition to the structural unit (VIII). The structural units derived from other monomers may be one type or two or more types. Examples of other monomers that may be contained in the (meth)acrylate polymer include monomers having polar functional groups, monomers having aromatic groups, and acrylamide monomers.

[0268] Examples of the monomer having a polar functional group include (meth)acrylates having a polar functional group. Examples of the polar functional group include a hydroxyl group, a carboxyl group, a substituted amino group or an unsubstituted amino group substituted by an alkyl group having 1 to 6 carbon atoms, and a heterocyclic group such as an epoxy group.

[0269] The content of the structural unit derived from the monomer having a polar functional group in the (meth)acrylate polymer is preferably 10 parts by mass or less, more preferably 0.5 parts by mass or more and 10 parts by mass or less, and further preferably 1 part by mass or more and 5 parts by mass or less, based on 100 parts by mass of all structural units of the (meth)acrylate polymer.

[0270] Examples of the monomer having an aromatic group include (meth)acrylates having one (meth)acryloyl group and one or more aromatic rings (eg, benzene ring, naphthalene ring, etc.) in the molecule and having a phenyl group, a phenoxyethyl group, or a benzyl group.

[0271] The content of the structural unit derived from the monomer having an aromatic group in the (meth)acrylate polymer is preferably 4 parts by mass or more and 20 parts by mass or less, and more preferably 4 parts by mass or more and 15 parts by mass or less, based on 100 parts by mass of all structural units of the (meth)acrylate polymer.

[0272] Examples of the acrylamide monomer include N-(methoxymethyl)acrylamide, N-(ethoxymethyl)acrylamide, N-(propoxymethyl)acrylamide, N-(butoxymethyl)acrylamide, and N-(2-methylpropoxymethyl)acrylamide.

[0273] In addition, structural units derived from other monomers other than structural unit (VIII) may include structural units derived from styrene-based monomers, structural units derived from vinyl-based monomers, and structural units derived from monomers having a plurality of (meth)acryloyl groups in the molecule.

[0274] The weight average molecular weight (hereinafter also referred to as "Mw") of the (meth)acrylic resin is preferably 500,000 to 2.5 million. If the weight average molecular weight is 500,000 or more, the durability of the adhesive layer in a high temperature and high humidity environment can be improved. If the weight average molecular weight is 2.5 million or less, the operability when applying a coating liquid containing an adhesive composition becomes good. The molecular weight distribution (Mw / Mn) represented by the ratio of the weight average molecular weight (Mw) to the number average molecular weight (hereinafter also referred to as "Mn") is usually 2 to 10. The so-called "weight average molecular weight" and "number average molecular weight" in this specification are polystyrene conversion values ​​measured by gel permeation chromatography (GPC).

[0275] When the (meth)acrylic resin is dissolved in ethyl acetate to prepare a solution having a concentration of 20% by mass, the viscosity at 25° C. is preferably 20 Pa·s or less, and more preferably 0.1 to 15 Pa·s. If the viscosity at 25° C. of the (meth)acrylic resin is within the above range, it contributes to the improvement of the durability and reworkability of the optical laminate including the adhesive layer formed using the resin. The above viscosity can be measured using a Brookfield viscometer.

[0276] The glass transition temperature (Tg) of the (meth)acrylic resin is, for example, -60 to 20° C., preferably -50 to 15° C., more preferably -45 to 10° C., and further preferably -40 to 0° C. The glass transition temperature can be measured by a differential scanning calorimeter (DSC).

[0277] The (meth)acrylic resin may contain two or more (meth)acrylate polymers. Examples of such (meth)acrylate polymers include (meth)acrylate polymers having a relatively low molecular weight of 50,000 to 300,000 and a structural unit (VIII) derived from the above (meth)acrylate as a main component and a weight average molecular weight in the range of 50,000 to 300,000.

[0278] (Meth) acrylic resins can be generally produced by known polymerization methods such as solution polymerization, bulk polymerization, suspension polymerization, and emulsion polymerization. In the production of (meth) acrylic resins, polymerization is generally carried out in the presence of a polymerization initiator. The amount of the polymerization initiator used is generally 0.001 to 5 parts by mass relative to 100 parts by mass of the total monomers constituting the (meth) acrylic resin.

[0279] The adhesive composition preferably contains a crosslinking agent. As the crosslinking agent, conventional crosslinking agents (such as isocyanate compounds, epoxy compounds, aziridine compounds, metal chelate compounds, peroxides, etc.) can be cited. In particular, isocyanate compounds are preferred from the viewpoints of the usable time of the adhesive composition, the crosslinking speed, and the durability of the polarizing plate. The proportion of the crosslinking agent is, for example, 0.01 to 10 parts by mass, preferably 0.05 to 5 parts by mass, relative to 100 parts by mass of the (meth)acrylic resin.

[0280] The adhesive composition may further contain a silane compound. The content of the silane compound in the adhesive composition is usually 0.01 to 10 parts by mass based on 100 parts by mass of the (meth)acrylic resin.

[0281] The adhesive composition may further include an antistatic agent. As the antistatic agent, a known antistatic agent can be cited, and an ionic antistatic agent is suitable. From the perspective of excellent stability of the antistatic performance of the adhesive composition over time, an ionic antistatic agent that is solid at room temperature is preferred. The content of the antistatic agent is preferably 0.01 to 20 parts by mass, more preferably 1 to 7 parts by mass, relative to 100 parts by mass of the (meth) acrylic resin.

[0282] The thickness of the pressure-sensitive adhesive layer is usually 0.1 to 30 μm, preferably 3 to 30 μm, and more preferably 5 to 25 μm.

[0283] The storage modulus of the adhesive layer at a temperature of 25°C is preferably 1.0×10 4 Pa~1.0×10 6 Pa, more preferably 1.0×10 4 Pa~1.0×10 5 Pa. The storage modulus can be obtained by dynamic viscoelasticity measurement.

[0284] The creep amount ΔCr of the adhesive layer at a temperature of 70°C is, for example, 65 μm or less, and may also be 50 μm or less, 45 μm or less, 40 μm or less, 35 μm or less, 30 μm or less, 25 μm or less, 20 μm or less, and may further be 15 μm or less. The lower limit of the creep amount ΔCr is, for example, 0.5 μm. If the creep amount is within this range, it is possible to suppress glue deficiency, glue stains, and poor cutting when cutting the optical laminate in the same manner as in the case of the storage modulus. It should be noted that the creep value can be measured, for example, using the following steps: to an adhesive layer attached to a stainless steel test plate with a joint surface of 20 mm in length and 20 mm in width, a load of 500 gf is applied vertically downward while the test plate is fixed. The creep amount (offset) of the adhesive layer relative to the test plate at each time 100 seconds and 3600 seconds after the start of the load application is measured and set as Cr respectively. 100 and Cr 3600 According to the measured Cr 100 and Cr 3600 , we can use the formula ΔCr=Cr 3600 -Cr 100 Calculate the creep amount ΔCr.

[0285] (Spacer)

[0286] The spacer is arranged to be able to be peeled off relative to the 3rd bonding layer for bonding the optical laminate to the display element, and the surface of the 3rd bonding layer is covered and protected. When the spacer is peeled off from the 3rd bonding layer of the optical laminate with the spacer, the spacer can be peeled off while keeping the shape of the 3rd bonding layer unchanged. As the spacer, it is preferred to have a base film and a release treatment layer. The base film can include a film obtained by film-forming a resin, and as the resin, for example, the film substrate used in the 1st base layer and the 2nd base layer can be included. The release treatment layer can be any known release treatment layer, and for example, a layer formed by applying a release agent such as a fluorine compound or a silicone compound to a base film can be included.

[0287] Example

[0288] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples. "%" and "parts" in Examples and Comparative Examples mean "mass %" and "mass parts" unless otherwise specified.

[0289] [Measurement of thickness]

[0290] The thickness of each layer was measured using a laser microscope (LEXT, manufactured by Olympus Corporation) or a digital micrometer “MH-15M” manufactured by Nikon Corporation, unless otherwise specified.

[0291] [Production of polarizing plate with substrate layer (1)]

[0292] (Preparation of the First Liquid Crystal Composition)

[0293] The following components were mixed and stirred at a temperature of 80° C. for 1 hour to obtain a first liquid crystal composition. The polymerizable liquid crystal compounds (X1) and (X2) have the structures shown below. The dichroic dyes (DP1) to (DP3) are azo dyes described in the examples of JP-A-2013-101328 and have the structures shown below.

[0294] Polymerizable liquid crystal compound (X1): 75 parts

[0295] Polymerizable liquid crystal compound (X2): 25 parts

[0296] Dichroic pigment (DP1): 2.5 parts

[0297] Dichroic pigment (DP2): 2.5 parts

[0298] Dichroic pigment (DP3): 2.5 parts

[0299] Polymerization initiator [2-dimethylamino-2-benzyl-1-(4-morpholinophenyl)butan-1-one (Irgacure (registered trademark) 369; manufactured by BASF Japan Co., Ltd.]: 6 parts

[0300] Leveling agent [polyacrylate compound (BYK-361N; manufactured by BYK-Chemie)]: 1.2 parts

[0301] Solvent [o-xylene]: 250 parts

[0302] ·Polymerizable liquid crystal compound (X1):

[0303] [Chemical formula 6]

[0304]

[0305] Polymerizable liquid crystal compound (X2):

[0306] [Chemical formula 7]

[0307]

[0308] Dichroic pigment (DP1):

[0309] [Chemical formula 8]

[0310]

[0311] ·Dichroic pigment (DP2):

[0312] [Chemical formula 9]

[0313]

[0314] ·Dichroic pigment (DP3):

[0315] [Chemical formula 10]

[0316]

[0317] (Preparation of Photo-Alignment Film-Forming Composition (1))

[0318] The following components described in Japanese Patent Application Laid-Open No. 2013-033249 were mixed, and the obtained mixture was stirred at 80° C. for 1 hour to obtain a composition (1) for forming a photo-alignment film.

[0319] · Photo-alignable polymer with the structure shown below: 2 parts

[0320] [Chemical formula 11]

[0321]

[0322] Solvent [o-xylene]: 98 parts

[0323] (Preparation of water-soluble polymer aqueous solution)

[0324] According to the following synthesis scheme, a water-soluble polymer containing the following structural units was obtained.

[0325] [Chemical formula 12]

[0326]

[0327] 20 g of polyvinyl alcohol (manufactured by Wako Pure Chemical Industries, Ltd.) with a molecular weight of 1000 and 0.55 mg of N,N-dimethyl-4-aminopyridine and 4.6 g of triethylamine as a nucleophilic agent were dissolved in 400 g of dimethyl sulfoxide, and the temperature was raised to 60°C while stirring. Subsequently, a solution in which 10.5 g of methacrylic anhydride was dissolved in 50 g of dimethyl sulfoxide was added dropwise over 1 hour, and the mixture was heated and stirred at 60°C for 14 hours to react. After the obtained reaction solution was cooled to room temperature, 481 g of methanol was added to the reaction solution and stirred until completely mixed, thereby adjusting the ratio (mass) of the reaction solution to methanol to 1:1. 1500 mL of acetone was slowly added to the solution, thereby crystallizing the water-soluble polymer by the crystallization method. The obtained solution containing white crystals was filtered, washed thoroughly with acetone, and then vacuum dried to obtain 20.2 g of a water-soluble polymer. The obtained water-soluble polymer was dissolved in water to prepare a 3 mass % water-soluble polymer aqueous solution.

[0328] (Preparation of HC layer forming composition)

[0329] The following components were mixed and stirred at a temperature of 50° C. for 4 hours to obtain a composition for forming a hard coating (HC) layer.

[0330] Acrylate monomer of the structure shown below: 70 parts

[0331] [Chemical formula 13]

[0332]

[0333] Urethane acrylate resin [EBECRYL4858 (manufactured by Daicel-Allnex Co., Ltd.)]: 30 parts

[0334] Polymerization initiator [Omnirad 907 (manufactured by IGM Resins BV)]: 3 parts

[0335] Solvent [methyl ethyl ketone]: 10 parts

[0336] (Production of Polarizing Plate (1) with Substrate Layer)

[0337] The composition for forming an HC layer obtained above was continuously applied to the release-treated surface of a roll-shaped release polyethylene terephthalate (PET) film ("FF-50" manufactured by UNITIKA Co., Ltd., a single-side release-treated PET film (thickness of the supporting substrate: 50 μm)) having a film width of 800 mm using a slot coater, and dried at a temperature of 100° C. for 2 minutes to form a HC layer (protective layer) having a thickness of 2.00 μm. Thus, a film having an HC layer laminated on the release-treated surface of the single-side release-treated PET film was obtained, which was used as the first substrate layer (1).

[0338] After the HC layer of the first substrate layer (1) was subjected to plasma treatment, the composition for forming a photo-alignment film (1) prepared above was applied using a slot coater to form a coating layer in a width of 600 mm in the central portion of the single-sided release-treated PET film. Next, the film was conveyed in a ventilation drying oven set at a temperature of 100° C. for 2 minutes to remove the solvent and dry the coating layer on the HC layer. Thereafter, the dried coating layer was subjected to a 20 mJ / cm 2 The single-sided release-treated PET film was irradiated with polarized UV light at an angle of 90° to the longitudinal direction at an intensity of 1.5 (313 nm reference) to impart an alignment regulating force, thereby forming a photo-alignment film (1) on the HC layer. The thickness of the photo-alignment film (1) was about 50 nm.

[0339] The first liquid crystal composition prepared above was applied to the photo-alignment film (1) formed on the first substrate layer (1) using a slit coater to form a coating layer in a width range of 600 mm in the central portion of the first substrate layer (1). Next, the coating layer was conveyed in a ventilation drying oven set at a temperature of 110° C. for 2 minutes to remove the solvent and dry the coating layer on the first substrate layer (1). Thereafter, a high-pressure mercury lamp was used to heat the coating layer at 1000 mJ / cm 2 The coating layer is irradiated with ultraviolet light (365 nm reference) to cure the polymerizable liquid crystal compound contained in the dried coating layer, thereby forming a cured layer of the first liquid crystal composition, and a liquid crystal polarizer (1) with a substrate layer is obtained, wherein a photo-alignment film (1) and a cured layer (together a liquid crystal polarizer) are sequentially formed on the first substrate layer (1). The liquid crystal polarizer (1) with a substrate layer has an absorption axis in a direction of 90° relative to the longitudinal direction. The thickness of the cured layer is 3 μm.

[0340] Then, after plasma treatment was applied to the liquid crystal polarizer side of the liquid crystal polarizer with substrate layer (1), the water-soluble polymer aqueous solution prepared above was continuously applied using a slot coater, and dried at a temperature of 100° C. for 2 minutes to form an outer coating layer (second protective layer) with a thickness of 2 μm. Thus, a long polarizing plate with substrate layer (1) having the first substrate layer (1) (single-sided release-treated PET film / HC layer) / liquid crystal polarizer (photo-alignment film (1) / cured material layer) / outer coating layer in this order was obtained.

[0341] The obtained polarizing plate (1) with a substrate layer was cut into a square of 40 mm×40 mm. The top coating side was bonded to an alkali-free glass plate (Corning, trade name “Eagle-XG”) using a 25 μm-thick acrylic adhesive (LINTEC Co., Ltd., trade name “P-3132”), and then the single-sided release-treated PET film was peeled off to obtain a test body.

[0342] The single transmittance (T1) in the transmission axis direction and the single transmittance (T2) in the absorption axis direction of the obtained test piece were measured in a wavelength range of 380 to 680 nm with a 2 nm step size using a spectrophotometer (UV-3150 manufactured by Shimadzu Corporation) equipped with a holder having a polarizing plate. The single transmittance at each wavelength and the degree of polarization were calculated using the following formulas (Formula 1) and (Formula 2), and then the visibility correction was performed using the 2 degree viewing field (C light source) of JIS Z 8701 to calculate the visibility corrected single transmittance (Ty) and the visibility corrected degree of polarization (Py).

[0343] Single body transmittance [%] = (T1 + T2) / 2 (Formula 1)

[0344] Polarization degree [%] = [(T1-T2) / (T1+T2)] × 100 (Formula 2)

[0345] As a result, the visibility-corrected single transmittance (Ty) of the test body was 42%, and the visibility-corrected polarization degree (Py) was 97%, which were confirmed to be useful values ​​for a polarizing plate. In addition, after heating the test body at a temperature of 100°C for 120 hours, the visibility-corrected single transmittance (Ty) and the visibility-corrected polarization degree (Py) were calculated using the above steps. As a result, the visibility-corrected single transmittance (Ty) of the heated test body was also 42%, and the visibility-corrected polarization degree (Py) was also 97%, and no decrease in optical performance was observed.

[0346] [Production of polarizing plate with substrate layer (2)]

[0347] A polarizing plate (2) with a substrate layer was produced by following the same production steps as for the polarizing plate (1) with a substrate layer, except that the thickness of the HC layer (protective layer) formed on the single-side release-treated PET film was changed to 3.95 μm.

[0348] [Production of polarizing plate with substrate layer (3)]

[0349] A polarizing plate (3) with a substrate layer was produced by the same process as that for producing the polarizing plate (1) with a substrate layer, except that the thickness of the HC layer (protective layer) formed on the single-side release-treated PET film was changed to 4.95 μm.

[0350] [Preparation of the first liquid crystal phase difference layer (1)]

[0351] (Preparation of Alignment Film-Forming Composition (1))

[0352] Water was added to commercially available polyvinyl alcohol (polyvinyl alcohol 1000 completely saponified type, manufactured by Wako Pure Chemical Industries, Ltd.), and the mixture was heated at 100° C. for 1 hour to obtain an alignment film-forming composition (1).

[0353] (Preparation of Second Liquid Crystal Composition (1))

[0354] The polymerizable liquid crystal compound (X3) and the polymerizable liquid crystal compound (X4) shown below are mixed, and the leveling agent, photopolymerization initiator and ionic compound shown below are added thereto, and then the solvent shown below is added to obtain a mixture. The mixture is stirred at a temperature of 80° C. for 1 hour, thereby preparing a second liquid crystal composition (1). The polymerizable liquid crystal compounds (X3) and (X4) are prepared according to the method described in Japanese Patent Publication No. 2010-244038 and have the structure shown below. The ionic compound has the structure shown below.

[0355] Polymerizable liquid crystal compound (X3): 80 parts

[0356] Polymerizable liquid crystal compound (X4): 20 parts

[0357] Leveling agent [MEGAFACE F-556 (manufactured by DIC Corporation)]: 0.1 part

[0358] Photopolymerization initiator [Omnirad 907 (manufactured by IGM Resin BV)]: 2.5 parts

[0359] Ionic compounds: 0.1 parts

[0360] Solvent [cyclopentanone]: 650 parts

[0361] Polymerizable liquid crystal compound (X3):

[0362] [Chemical formula 14]

[0363]

[0364] Polymerizable liquid crystal compound (X4):

[0365] [Chemical formula 15]

[0366]

[0367] Ionic compounds:

[0368] [Chemical formula 16]

[0369]

[0370] (Preparation of the First Liquid Crystal Retardation Layer (1) with a Substrate Layer)

[0371] A cycloolefin polymer (COP) film (ZF14, manufactured by ZEON Co., Ltd., Japan) cut into a rectangular shape was subjected to a corona treatment using a corona treatment device (AGF-B10; manufactured by Kasuga Electric Co., Ltd.), and then coated with an alignment film-forming composition (1). After heating and drying, an alignment film having a thickness of 100 nm was formed. The surface of the resulting alignment film was subjected to a rubbing treatment at an angle of 75° relative to the long side direction of the COP film, and the second liquid crystal composition (1) was coated on the surface using a bar coater. The resulting coating film was dried at a temperature of 120°C for 2 minutes, and then irradiated with an exposure amount of 1000 mJ / cm at a temperature of 80°C in a nitrogen atmosphere using a high-pressure mercury lamp ("UNICURE VB-15201BY-A" manufactured by USHIO Electric Co., Ltd.). 2 The polymerizable liquid crystal compound is cured under ultraviolet light (365 nm reference) to form a cured product layer (1-1) of the polymerizable liquid crystal compound, which is cured in a state where the optical axis of the polymerizable liquid crystal compound is oriented in a horizontal direction relative to the COP film surface. Thus, a first liquid crystal retardation layer (1) with a substrate layer is obtained, which includes a second substrate layer (COP film) / a first liquid crystal retardation layer (1) (oriented film / cured product layer (1-1)).

[0372] The thickness of the obtained cured layer (1-1) was measured using a laser microscope and the result was 2 μm. The in-plane phase difference value of the first liquid crystal phase difference layer (1) was measured using KOBRA-WR manufactured by Prince Instruments Co., Ltd. As a result, the in-plane phase difference value at a wavelength of 550 nm was Re (550) = 270 nm. It should be noted that since the phase difference value of the COP film at a wavelength of 550 nm is approximately 0, the COP film has no effect on the optical properties of the first liquid crystal phase difference layer (1). The orientation angle relative to the long side direction of the COP film is -15°.

[0373] [Preparation of the Second Liquid Crystal Retardation Layer (1)]

[0374] (Preparation of Second Liquid Crystal Composition (2))

[0375] The polymerizable liquid crystal compound (X5), a leveling agent, and a photopolymerization initiator shown below were mixed, and then the solvent shown below was mixed, and stirred at a temperature of 80° C. for 1 hour to prepare a second liquid crystal composition (2). The polymerizable liquid crystal compound (X5) has the structure shown below.

[0376] Polymerizable liquid crystal compound (X5) [Paliocolor LC242 (manufactured by BASF JAPAN)]: 100 parts

[0377] Leveling agent [BYK-361N (manufactured by BYK-Chemie)]: 0.1 part

[0378] Photopolymerization initiator [Omnirad 907 (manufactured by IGM Resin BV)]: 2.5 parts

[0379] Solvent [propylene glycol 1-monomethyl ether 2-acetate (PGME)]: 400 parts

[0380] Polymerizable liquid crystal compound (X5):

[0381] [Chemical formula 17]

[0382]

[0383] (Preparation of the Second Liquid Crystal Retardation Layer (1) with Substrate Layer)

[0384] The composition for forming an alignment film (1) is applied to a triacetylcellulose (TAC) film (manufactured by Konica Minolta Co., Ltd., KC4UY) cut into a rectangular shape, and after heating and drying, an alignment film with a thickness of 100 nm is formed. The surface of the obtained alignment film is subjected to a rubbing treatment at an angle of 15° relative to the long side direction of the TAC film, and the second liquid crystal composition (2) is applied to the surface using a rod coater. The obtained coating film is dried at a temperature of 100°C for 1 minute, and then cooled to room temperature to obtain a dry film. Then, a high-pressure mercury lamp ("UNICURE VB-15201BY-A" manufactured by USHIO Electric Co., Ltd.) is used to irradiate the dry film with an exposure amount of 1000mJ / cm in a nitrogen atmosphere. 2 The polymerizable liquid crystal compound is cured under ultraviolet light (365 nm reference) to form a cured product layer (2-1) of the polymerizable liquid crystal compound, which is cured in a state where the optical axis of the polymerizable liquid crystal compound is oriented in a horizontal direction relative to the TAC film surface. Thus, a second liquid crystal retardation layer (1) with a substrate layer is obtained, which includes a second substrate layer (TAC film) / a second liquid crystal retardation layer (1) (oriented film / cured product layer (2-1) (horizontally oriented liquid crystal cured film)).

[0385] The thickness of the obtained cured layer (2-1) was measured using a laser microscope and found to be 1 μm. The in-plane phase difference value of the second liquid crystal phase difference layer (1) was measured using KOBRA-WR manufactured by Prince Instruments Co., Ltd. As a result, the in-plane phase difference value at a wavelength of 550 nm was Re (550) = 140 nm. It should be noted that since the phase difference value of the TAC film at a wavelength of 550 nm is approximately 0, the TAC film has no effect on the optical properties of the second liquid crystal phase difference layer (1). The orientation angle relative to the long side direction of the TAC film is 75°.

[0386] [Preparation of the first liquid crystal phase difference layer (2)]

[0387] (Preparation of Photo-Alignment Film-Forming Composition (2))

[0388] 2 parts of a photo-alignment material having the structure shown below were mixed with 98 parts of cyclopentanone (solvent) and stirred at 80° C. for 1 hour to obtain a photo-alignment film-forming composition (2). A photo-alignment material having the structure shown below (weight average molecular weight: 50,000, m:n=50:50) was synthesized according to the method described in Japanese Patent Application Laid-Open No. 2021-196514.

[0389] Photo-oriented materials:

[0390] [Chemical formula 18]

[0391]

[0392] (Preparation of Second Liquid Crystal Composition (3))

[0393] The polymerizable liquid crystal compound (X6), polymerizable liquid crystal compound (X7), leveling agent and photopolymerization initiator shown below are mixed, and then N-methyl-2-pyrrolidone (NMP) is mixed so that the solid content concentration is 13%, and stirred at a temperature of 80°C for 1 hour to prepare a second liquid crystal composition (3). The polymerizable liquid crystal compound (X6) and the polymerizable liquid crystal compound (X7) have the structures shown below. The polymerizable liquid crystal compound (X6) is prepared in the same manner as described in Japanese Patent Application Laid-Open No. 2019-003177. The polymerizable liquid crystal compound (X7) is prepared in the same manner as described in Japanese Patent Application Laid-Open No. 2009-173893.

[0394] Polymerizable liquid crystal compound (X6): 90 parts

[0395] Polymerizable liquid crystal compound (X7): 10 parts

[0396] Leveling agent [BYK-361N (made by BM Chemie)]: 0.1 part

[0397] Photopolymerization initiator [Irgacure OXE-03 (manufactured by BASF Japan Co., Ltd.)]: 3 parts

[0398] Polymerizable liquid crystal compound (X6):

[0399] [Chemical formula 19]

[0400]

[0401] Polymerizable liquid crystal compound (X7):

[0402] [Chemical formula 20]

[0403]

[0404] 1 mg of the polymerizable liquid crystal compound (X6) was dissolved in 10 mL of chloroform to obtain a solution. A measurement sample was added to a measurement cell having an optical path length of 1 cm, and the measurement sample was placed in an ultraviolet-visible spectrophotometer ("UV-2450" manufactured by Shimadzu Corporation) to measure the absorption spectrum. The wavelength at which the maximum absorbance was reached was read from the obtained absorption spectrum, and the result showed that the maximum absorption wavelength λmax in the wavelength range of 300 to 400 nm was 356 nm.

[0405] (Preparation of the First Liquid Crystal Retardation Layer (2) with Substrate Layer)

[0406] A composition (2) for forming a photo-alignment film was applied to a biaxially stretched polyethylene terephthalate (PET) film (DIAFOIL, manufactured by Mitsubishi Plastics Co., Ltd.) using a rod coater. The obtained coating layer was dried at a temperature of 120°C for 2 minutes, cooled to room temperature, and dried. Thereafter, the dried coating layer was irradiated with 100 mJ (313 nm reference) of polarized ultraviolet light using a UV irradiation device (SPOT CURE SP-9; manufactured by USHIO Electric Co., Ltd.) to obtain a photo-alignment film (2). The thickness of the photo-alignment film (2) measured using an ellipsometer M-220 manufactured by JASCO Corporation was 100 nm.

[0407] The second liquid crystal composition (3) prepared above was applied to the photo-alignment film (2) on the PET film using a bar coater to form a coating layer. The coating layer was dried at 120°C for 2 minutes and then cooled to room temperature. The dried coating layer was irradiated with a high-pressure mercury lamp ("UNICURE VB-15201BY-A" manufactured by USHIO Electric Co., Ltd.) in a nitrogen atmosphere at an exposure dose of 500 mJ / cm 2 The polymerizable liquid crystal compound was cured in a state of being oriented in a horizontal direction relative to the PET film surface by ultraviolet light (365 nm), thereby forming a cured layer (1-2) of the second liquid crystal composition (3). The thickness of the cured layer (1-2) measured using a laser microscope LEXT OLS4100 manufactured by Olympus Corporation was 2 μm. Thus, a first liquid crystal retardation layer (2) with a substrate layer, comprising a second substrate layer (PET film) / a first liquid crystal retardation layer (2) (photo-alignment film (2) / cured layer (1-2)), was obtained.

[0408] The first liquid crystal phase difference layer (2) with a substrate layer was subjected to a corona treatment on its side, and the first liquid crystal phase difference layer (2) with a substrate layer was bonded to glass via a 25 μm pressure-sensitive adhesive manufactured by LINTEC, and the PET film was peeled off to obtain a test body. The in-plane phase difference value of the test body was measured using KOBRA-WR manufactured by Oji Instruments Co., Ltd. The in-plane phase difference values ​​for light with wavelengths of 450 nm, 550 nm, and 650 nm were calculated using the Cauchy dispersion formula obtained from the measurement results of the in-plane phase difference values ​​for light with wavelengths of 448.2 nm, 498.6 nm, 548.4 nm, 587.3 nm, 628.7 nm, and 748.6 nm. As a result, the in-plane phase difference values ​​were Re (450) = 122 nm, Re (550) = 140 nm, and Re (650) = 144 nm, and the relationship between the in-plane phase difference values ​​at each wavelength is as follows.

[0409] Re(450) / Re(550)=0.87

[0410] Re(650) / Re(550)=1.03

[0411] [In the formula, Re(450) represents the in-plane phase difference value for light with a wavelength of 450nm, Re(550) represents the in-plane phase difference value for light with a wavelength of 550nm, and Re(650) represents the in-plane phase difference value for light with a wavelength of 650nm.]

[0412] [Preparation of the second liquid crystal phase difference layer (2)]

[0413] (Preparation of Vertical Alignment Film Forming Composition)

[0414] 2-Phenoxyethyl acrylate, tetrahydrofurfuryl acrylate, dipentaerythritol triacrylate and bis(2-vinyloxyethyl) ether were mixed at a ratio of 1:1:4:5, and then LUCIRIN TPO was added as a polymerization initiator at a ratio of 4% to prepare a composition for forming a vertical alignment film.

[0415] (Preparation of Second Liquid Crystal Composition (4))

[0416] A second liquid crystal composition (4) was prepared using a photopolymerizable nematic liquid crystal compound (RMM28B manufactured by Merck) and a solvent so that the solid content was 1 to 1.5 g. The solvent used was a mixed solvent obtained by mixing methyl ethyl ketone (MEK), methyl isobutyl ketone (MIBK) and cyclohexanone (CHN), wherein the mass ratio of methyl ethyl ketone (MEK):MIBK:CHN was 35:30:35.

[0417] (Preparation of the Second Liquid Crystal Retardation Layer (2) with Substrate Layer)

[0418] A roll-shaped release polyethylene terephthalate (PET) film ("FF-50" manufactured by UNITIKA Co., Ltd., a single-sided release-treated PET film (thickness of the supporting substrate: 50 μm)) with a film width of 800 mm was subjected to a corona treatment on the surface opposite to the release-treated side, and then the vertical alignment film-forming composition prepared above was applied using a slot coater so that the thickness after curing was 3 μm. The coated film was irradiated with 200 mJ / cm 2 Ultraviolet rays are used to form a vertically oriented film on the single-sided release-treated PET film.

[0419] The second liquid crystal composition (4) prepared above was coated on the vertical alignment film on the single-sided release-treated PET film using a slit coater so that the thickness after curing was 1 μm. The drying temperature was set to 75°C and the drying time was set to 120 seconds. After the coating layer was dried, ultraviolet (UV) irradiation was performed to polymerize the polymerizable liquid crystal compound to form a cured layer (2-2). Thus, a second liquid crystal retardation layer (2) with a substrate layer was obtained, which included a second substrate layer (single-sided release-treated PET film) / a second liquid crystal retardation layer (2) (vertical alignment film / cured layer (2-2)). The second liquid crystal retardation layer (2) was a positive C plate.

[0420] [Preparation of Active Energy Ray-Curable Composition (1) (Cationically Polymerizable Adhesive Composition)]

[0421] The following components were mixed and degassed to prepare an active energy ray-curable composition (1). The photocationic polymerization initiator was added in the form of a 50% propylene carbonate solution, and the amount thereof is expressed as a solid content.

[0422] Cationic polymerizable compound (1) [3-ethyl-3{[(3-ethyloxetan-3-yl)methoxy]methyl}oxetane (trade name: OXT-221, manufactured by Toagosei Co., Ltd.)]: 60.0 parts

[0423] Cationic polymerizable compound (2) [3',4'-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate (trade name: CEL2021P, manufactured by Daicel Corporation)]: 32.5 parts

[0424] Cationic polymerizable compound (3) [1,2-epoxy-4-(2-epoxyethyl)cyclohexane adduct of 2,2-bis(hydroxymethyl)-1-butanol (trade name: EHPE3150, manufactured by Daicel Corporation)]: 7.5 parts

[0425] · Photocationic polymerization initiator [CPI-100P (San-Apro Co., Ltd., 50 mass % solution)]: 2.3 parts

[0426] Photosensitizer [9,10-dibutoxyanthracene]: 1.0 part

[0427] · Photosensitizer [1,4-diethoxynaphthalene]: 1.0 part

[0428] [Preparation of Active Energy Ray-Curable Composition (2) (Radially Polymerizable Adhesive Composition)]

[0429] The following components were mixed to prepare an active energy ray-curable composition (2).

[0430] · N,N-dimethylacrylamide [KJ Chemicals Co., Ltd.]: 65 parts

[0431] Dicyclopentyl acrylate [Hitachi Chemical Co., Ltd.]: 15 parts

[0432] · Ultraviolet curing urethane acrylate resin [trade name: UV-3700B, manufactured by Nippon Synthetic Chemical Industry Co., Ltd., viscosity: 30,000 to 60,000 mPa·s / 60°C, molecular weight (Mw): 38,000, number of oligomer functional groups: 2, glass transition temperature Tg: -6°C]: 20 parts

[0433] · Photoradical polymerization initiator [Omnirad 819 (2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropane-1-one), BASF JAPAN (KK)]: 3 parts

[0434] [Preparation of Adhesive Layer (1)]

[0435] In a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, a dropping device and a nitrogen inlet tube, 95.0 parts of n-butyl acrylate, 4.0 parts of acrylic acid, 1.0 parts of 2-hydroxyethyl acrylate, 200 parts of ethyl acetate and 0.08 parts of 2,2'-azobisisobutyronitrile were added, and the air in the reaction vessel was replaced with nitrogen. The reaction solution was heated to 60°C while stirring under a nitrogen atmosphere, reacted for 6 hours, and then cooled to room temperature.

[0436] The weight average molecular weight of a portion of the obtained solution was measured, and as a result, it was confirmed that a (meth)acrylate polymer of 1.8 million was generated. The weight average molecular weight (Mw) of the (meth)acrylic resin is a polystyrene-equivalent weight average molecular weight measured using gel permeation chromatography (GPC) under the following conditions.

[0437] [Measurement conditions]

[0438] ·GPC measuring apparatus: HLC-8020 manufactured by Tosoh Corporation

[0439] ·GPC column (passed in the following order): manufactured by Tosoh Corporation

[0440] TSK guard column HXL-H

[0441] TSK gel GMHXL (×2)

[0442] TSK gel G2000HXL

[0443] · Determination solvent: tetrahydrofuran

[0444] ·Measurement temperature: 40℃

[0445] 100 parts of the (meth)acrylate polymer obtained in the above step (solid content conversion value; the same shall apply hereinafter), 1.5 parts of trimethylolpropane-modified toluene diisocyanate (manufactured by TOSOH Corporation, trade name "CORONATE (registered trademark) L") as an isocyanate crosslinking agent, 0.30 parts of 3-glycidoxypropyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd., trade name "KBM403") as a silane coupling agent, 7.5 parts of ethoxylated isocyanuric acid triacrylate (manufactured by Shin-Nakamura Chemical Co., Ltd.: product name "A-9300") as an ultraviolet curable compound, and 0.5 parts of 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropane-1-one (manufactured by BASF: Irgacure (registered trademark) 907) as a photopolymerization initiator were mixed, stirred thoroughly, and diluted with ethyl acetate to obtain a coating solution of the adhesive composition (1).

[0446] The coating solution of the adhesive composition (1) was applied to the release treated surface (release layer) of the spacer (manufactured by LINTEC Co., Ltd.: SP-PLR382190) by a coating machine so that the thickness after drying was 5 μm (measured by a digital micrometer "MH-15M" manufactured by Nikon Co., Ltd.), and then dried at a temperature of 100° C. for 1 minute. Another spacer (manufactured by LINTEC Co., Ltd.: SP-PLR381031) was attached to the surface of the dried coating layer opposite to the surface to which the spacer was attached. The coating layer was irradiated with ultraviolet rays (irradiation intensity 500 mW / cm2) through the release sheet using an ultraviolet irradiation device with a conveyor (manufactured by Fusion UV Systems, Inc., using a D lamp). 2 、Accumulated light intensity 500mJ / cm 2 ) to form an adhesive layer (1), thereby obtaining an adhesive layer (1) with spacers on both sides.

[0447] The water vapor permeability of the adhesive layer (1) was measured at a temperature of 40°C and a relative humidity of 90% using a water vapor permeability meter (Lyssy-L80-5000 manufactured by Lyssy) and the result was 7600 g / (m 2 ·24h).

[0448] The storage modulus G' of the adhesive layer (1) was measured to be 125,000 Pa at a temperature of 25°C. The storage modulus G' was measured by laminating a plurality of adhesive layers (1) to a thickness of 0.2 mm (measured using a digital micrometer "MH-15M" manufactured by Nikon Corporation), punching out a cylindrical body having a diameter of 8 mm, using the obtained material as a measurement sample, and measuring the measurement sample using a viscoelasticity measuring device (manufactured by Physica Corporation, MCR300) in accordance with JIS K7244-6 by a torsional shear method under the following conditions.

[0449] [Measurement conditions]

[0450] Normal force FN: 1N

[0451] Strain γ: 1%

[0452] Frequency: 1Hz

[0453] Temperature: 25℃

[0454] The glass transition temperature of the adhesive layer (1) was measured by the following procedure, and the result was 25°C or less. First, 5 mg of the adhesive layer (1) was collected, placed in an aluminum press-top container, and sealed by pressing to prepare a measurement sample. The container containing the above-mentioned measurement sample was set in a differential scanning calorimeter (DSC) ["EXSTAR-6000 DSC6220" sold by SII NANO TECHNOLOGY Co., Ltd."], and the temperature was lowered from 20°C to -60°C while purging nitrogen. After reaching -60°C, it was maintained for 1 minute, and then the temperature was raised from -60°C to 150°C at a heating rate of 10°C / min. After reaching 150°C, the temperature was immediately lowered to 20°C. Thereafter, the midpoint glass transition temperature specified in JIS K 7121-1987 "Determination of Transition Temperatures of Plastics" was determined from the DSC curve when the temperature was raised from -60°C to 150°C, and this was taken as the glass transition temperature of the pressure-sensitive adhesive layer (1) to be measured.

[0455] [Preparation of Adhesive Layers (2) to (4)]

[0456] In a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, a dropping device and a nitrogen inlet tube, 97.0 parts of n-butyl acrylate, 1.0 parts of acrylic acid, 0.5 parts of 2-hydroxyethyl acrylate, 200 parts of ethyl acetate and 0.08 parts of 2,2'-azobisisobutyronitrile were added, and the air in the reaction vessel was replaced with nitrogen. The reaction solution was heated to 60°C while stirring under a nitrogen atmosphere, reacted for 6 hours, and then cooled to room temperature. The weight average molecular weight of a portion of the obtained solution was measured using the above steps, and as a result, it was confirmed that a (meth)acrylate polymer of 1.8 million was generated.

[0457] 100 parts (solid content conversion value; the same shall apply hereinafter) of the (meth)acrylate polymer obtained in the above step, 0.30 parts of trimethylolpropane-modified toluene diisocyanate (manufactured by TOSOH Corporation, trade name "CORONATE (registered trademark) L") as an isocyanate-based crosslinking agent, and 0.30 parts of 3-glycidoxypropyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd., trade name "KBM403") as a silane coupling agent were mixed, stirred thoroughly, and diluted with ethyl acetate to obtain a coating solution of an adhesive composition (2).

[0458] The coating solution of the adhesive composition (2) was applied to the release treated surface (peeling layer) of the spacer (manufactured by LINTEC Co., Ltd.: SP-PLR382190) using a coater so that the thickness after drying was 15 μm (adhesive layer (2)), 25 μm (adhesive layer (3)) and 35 μm (adhesive layer (4)) respectively (the thickness was measured using a digital micrometer "MH-15M" manufactured by Nikon Co., Ltd.), and then dried at a temperature of 100°C for 1 minute. Another spacer (manufactured by LINTEC Co., Ltd.: SP-PLR381031) was bonded to the surface of the dried coating layer opposite to the surface to which the spacer was bonded, thereby obtaining adhesive layers (2) to (4) with spacers on both sides.

[0459] The storage modulus G' of the adhesive layers (2) to (4) was measured by the above procedure and was 25500 Pa at a temperature of 25°C. The glass transition temperature of the adhesive layers (2) to (4) was measured by the above procedure and was 25°C or less.

[0460] [Example 1]

[0461] (Preparation of Phase Difference Laminated Body (1) with Base Layer)

[0462] The first liquid crystal phase difference layer side (1) of the first liquid crystal phase difference layer (1) with a substrate layer obtained above and the second liquid crystal phase difference layer (1) side of the second liquid crystal phase difference layer (1) with a substrate layer are respectively subjected to corona treatment. The corona-treated surfaces are bonded to each other via an adhesive layer (1) obtained by peeling off a spacer of an adhesive layer (1) with a spacer on both sides, thereby obtaining a phase difference laminate (1) with a substrate layer (phase difference body (1)). The phase difference laminate (1) with a substrate layer has a layer structure of second substrate layer (COP film) / first liquid crystal phase difference layer (1) (oriented film / cured material layer (1-1)) / second bonding layer (adhesive layer (1)) / second liquid crystal phase difference layer (1) (cured material layer (2-1) / oriented film) / second substrate layer (TAC film).

[0463] (Production of optical layered body (1) with spacer)

[0464] The outer coating side of the polarizing plate (1) with a substrate layer cut out from the long strip of the polarizing plate (1) with a substrate layer obtained above in such a way that the length direction of the long strip is the long side is subjected to corona treatment. Then, the second substrate layer (COP film) on the side of the first liquid crystal phase difference layer (1) of the phase difference stack (c1) with a substrate layer obtained above is peeled off, and the peeled surface is subjected to corona treatment. When the second substrate layer is peeled off, the oriented film is also peeled off. The above-mentioned corona-treated surfaces are bonded to each other via the active energy ray-curable composition (1) prepared above in such a way that the long sides overlap with each other. Then, from the side of the polarizing plate (1) with a substrate layer, a cumulative light amount of UVA is about 350mJ / cm 2 The active energy ray-curable composition (1) was cured by irradiating with ultraviolet light in a manner of 0.1% (measured value obtained by measuring device: UVPower PuckII manufactured by FusionUV) to form a first laminating layer as a cured layer. The thickness of the first laminating layer was 2 μm.

[0465] Thereafter, an adhesive layer (2) exposed by peeling off one spacer from an adhesive layer (2) with spacers on both sides is laminated to the surface of the second liquid crystal phase difference layer (1) with a substrate layer, and the single-sided release-treated PET film on the side of the polarizing plate (1) with a substrate layer is peeled off to obtain an optical laminate (1) with a spacer. When the second substrate layer is peeled off, the alignment film is also peeled off. The optical laminate (1) with a spacer has a layer structure of protective layer (HC layer) / liquid crystal polarizer (light alignment film (1) / cured layer) / overcoat layer / first laminating layer (cured layer of active energy ray-curable composition (1)) / first liquid crystal phase difference layer (1) (cured layer (1-1)) / second laminating layer (adhesive layer (1)) / second liquid crystal phase difference layer (1) (cured layer (2-1)) / third laminating layer (adhesive layer (2)) / spacer.

[0466] [Example 2]

[0467] The polarizing plate (1) with a substrate layer and the phase difference laminate (1) with a substrate layer are bonded together via an active energy ray curable composition (2), and the active energy ray curable composition (2) is cured at a cumulative UVB light intensity of about 250 mJ / cm 2 An optical layered body (2) with a spacer was obtained in the same manner as in Example 1 except that ultraviolet rays were irradiated as shown in FIG. 1 (measurement value obtained by measuring device: UV Power Puck II manufactured by FusionUV).

[0468] [Example 3]

[0469] (Preparation of Phase Difference Laminated Body (3) with Base Material Layer)

[0470] The first liquid crystal phase difference layer side (2) of the first liquid crystal phase difference layer (2) with a substrate layer obtained above and the second liquid crystal phase difference layer (2) side of the second liquid crystal phase difference layer (2) with a substrate layer are subjected to corona treatment. The adhesive layer (1) obtained by peeling off the spacer of the adhesive layer (1) with spacers on both sides is bonded to the corona treated surface to obtain a phase difference laminate (3) with a substrate layer (phase difference body (3)). The phase difference laminate (3) with a substrate layer has a layer structure of second substrate layer (PET film) / first liquid crystal phase difference layer (2) (photo-alignment film (2) / cured layer (1-2)) / second bonding layer (adhesive layer (1)) / second liquid crystal phase difference layer (2) (cured layer (2-2) / vertical alignment film) / second substrate layer (single-sided release-treated PET film).

[0471] (Preparation of optical layered body (3) with spacer)

[0472] The outer coating side of the polarizing plate (1) with a substrate layer obtained above is subjected to a corona treatment. Then, the second substrate layer (PET film) on the first liquid crystal phase difference layer (2) side of the phase difference laminate (3) with a substrate layer obtained above is peeled off, and the peeled surface is subjected to a corona treatment. During the peeling of the second substrate layer, the PET film is peeled off, and the photo-alignment film (2) is not peeled off, but remains on the cured layer (1-2). The above-mentioned corona-treated surfaces are bonded to each other via the active energy ray-curable composition (2) prepared above. Next, from the side of the polarizing plate (1) with a substrate layer, the accumulated light amount of UVA is about 250mJ / cm 2 The active energy ray-curable composition (2) was cured by irradiating with ultraviolet light in a manner of (measurement value obtained by measuring device: UV Power Puck II manufactured by FusionUV) to form a first laminating layer as a cured layer. The thickness of the first laminating layer was 2 μm.

[0473] Thereafter, the adhesive layer (2) exposed by peeling off one spacer from the adhesive layer (2) with spacers on both sides is laminated to the surface of the second liquid crystal retardation layer (2) with a substrate layer exposed by peeling off the second substrate layer (single-sided release-treated PET film), and the single-sided release-treated PET film on the side of the polarizing plate (1) with a substrate layer is peeled off to obtain an optical laminate (3) with a spacer. Due to the peeling off of the second substrate layer, the single-sided release-treated PET film is peeled off, and the vertical alignment film is not oriented but remains on the cured product layer (2-2). The optical laminate (3) with a spacer has a layer structure of protective layer (HC layer) / liquid crystal polarizer (photo-alignment film (1) / cured layer) / overcoat layer / first laminating layer (cured layer of active energy ray-curable composition (2)) / first liquid crystal retardation layer (2) (photo-alignment film (2) / cured layer (1-2)) / second laminating layer (adhesive layer (1)) / second liquid crystal retardation layer (2) (cured layer (2-2) / vertical alignment film) / third laminating layer (adhesive layer (2)) / spacer.

[0474] [Examples 4 to 6]

[0475] Optical layered bodies (4) to (6) with a separator were obtained in the same manner as in Example 3 except that the polarizing plates with substrate layers and the third bonding layer shown in Tables 2 and 3 were used.

[0476] [Example 7]

[0477] A separator-attached optical layered body (7) was obtained in the same manner as in Example 2 except that the third bonding layer shown in Table 3 was used as the third bonding layer.

[0478] [Comparative Example 1]

[0479] (Preparation of Adhesive Composition)

[0480] The following components were mixed and degassed to prepare a cationic polymerization type adhesive composition. The cationic polymerization initiator was blended as a 50 mass % propylene carbonate solution, and the solid content thereof is shown.

[0481] 1,6-Hexanediol diglycidyl ether (EX-212L, manufactured by Nagase ChemteX Co., Ltd.): 25 parts

[0482] 4-Hydroxybutyl vinyl ether: 10 parts

[0483] ·Bisphenol F type epoxy resin (EXA-830CRP, manufactured by DIC Corporation): 65 parts

[0484] Cationic polymerization initiator (CPI-100P, manufactured by San-Apro Co., Ltd., 50% by mass solution): 3 parts

[0485] (Preparation of Phase Difference Laminated Body (c1) with Base Layer)

[0486] The first liquid crystal retardation layer (2) with a substrate layer obtained above and the second liquid crystal retardation layer (2) with a substrate layer were laminated via the active energy ray-curable composition (1) prepared above in such a manner that the first liquid crystal retardation layer side (2) and the second liquid crystal retardation layer (2) side were the bonding surfaces, respectively. Then, ultraviolet rays were irradiated from the second liquid crystal retardation layer (2) with a substrate layer side to cure the active energy ray-curable composition (1) to form a second bonding layer with a thickness of 2 μm, thereby obtaining a retardation laminate (c1) with a substrate layer (retardation body (c1)). The phase difference laminate (c1) with substrate layer has a layer structure of second substrate layer (PET film) / first liquid crystal phase difference layer (2) (photo-alignment film (2) / cured layer (1-2)) / second laminating layer (cured layer of active energy ray-curable composition (1)) / second liquid crystal phase difference layer (2) (cured layer (2-2) / vertical alignment film) / second substrate layer (single-sided release-treated PET film).

[0487] (Production of optical layered body (c1) with spacer)

[0488] The outer coating side of the polarizing plate (1) with a substrate layer obtained above is subjected to a corona treatment. Then, the second substrate layer (PET film) on the first liquid crystal phase difference layer (2) side of the phase difference laminate (c1) with a substrate layer obtained above is peeled off, and the peeled surface is subjected to a corona treatment. During the peeling of the second substrate layer, the PET film is peeled off, and the photo-alignment film (2) is not peeled off, but remains on the cured layer (1-2). The above-mentioned corona-treated surfaces are bonded to each other via the adhesive layer (1) obtained by peeling off the spacer of the adhesive layer (1) with a spacer on both sides, to obtain a laminated structure (c1).

[0489] A 13.00 μm thick cycloolefin polymer (COP) film (ZF14 manufactured by ZEON Co., Ltd., Japan) and the exposed surface of the laminated structure (c1) obtained above by peeling off the single-sided release-treated PET film on the side of the polarizing plate (1) with the substrate layer were subjected to corona treatment. The corona-treated surfaces were bonded to each other via the adhesive composition prepared above, and irradiated with an ultraviolet irradiation device (SPOT CURE SP-7 manufactured by USHIO Electric Co., Ltd.) at an exposure dose of 500 mJ / cm 2 The adhesive layer with a thickness of 2.00 μm was formed by irradiating the adhesive layer with ultraviolet light (365 nm reference) from the COP film side. The ultraviolet light was irradiated from the COP film side. Subsequently, the adhesive layer (2) exposed by peeling off one spacer from the adhesive layer (2) with spacers on both sides was bonded to the surface of the second liquid crystal phase difference layer (2) with a substrate layer exposed by peeling off the second substrate layer, thereby obtaining an optical laminate (c1) with a spacer. Due to the peeling off of the second substrate layer, the single-sided release-treated PET film was peeled off, and the vertical alignment film was not oriented, but remained on the cured layer (2-2). The optical laminate (c1) with a spacer has a layer structure of protective layer (COP film / adhesive layer / HC layer) / liquid crystal polarizer (photo-alignment film (1) / cured layer) / overcoat layer / first laminating layer (adhesive layer (1)) / first liquid crystal retardation layer (2) (photo-alignment film (2) / cured layer (1-2)) / second laminating layer (cured layer of active energy ray-curable composition (1)) / second liquid crystal retardation layer (2) (cured layer (2-2) / vertical alignment film) / third laminating layer (adhesive layer (2)) / spacer.

[0490] [Comparative Example 2]

[0491] A triacetyl cellulose (TAC) film (KC2CT, manufactured by Konica Minolta Co., Ltd.) with a thickness of 20.00 μm was used instead of the COP film, and the TAC film was bonded to the surface exposed by peeling off the single-sided release-treated PET film from the laminated structure (c1), and ultraviolet rays were irradiated from the TAC film side. In addition, the optical laminate (c2) with a spacer was obtained by the production steps of the optical laminate (c2) with a spacer of Comparative Example 1.

[0492] [Comparative Example 3]

[0493] The outer coating side of the long strip of polarizing plate (1) with a substrate layer cut out from the long strip of polarizing plate (1) with a substrate layer obtained above in such a manner that the length direction of the long strip is the long side is subjected to corona treatment. Next, the second substrate layer (COP film) on the side of the first liquid crystal phase difference layer (1) of the phase difference laminate (1) with a substrate layer obtained by the steps of Example 1 is peeled off, and the peeled surface is subjected to corona treatment. When the second substrate layer is peeled off, the alignment film is also peeled off. The above-mentioned corona-treated surfaces are laminated to each other in such a manner that the long sides overlap each other, and the adhesive layer (1) obtained by peeling off the spacer of the adhesive layer (1) with a spacer on both sides is bonded.

[0494] Thereafter, an adhesive layer (3) exposed by peeling off one spacer from an adhesive layer (3) with spacers on both sides is laminated to the surface of the second liquid crystal phase difference layer (1) with a substrate layer, and the single-sided release-treated PET film on the side of the polarizing plate (1) with a substrate layer is peeled off to obtain an optical laminate (c3) with a spacer. When the second substrate layer is peeled off, the alignment film is also peeled off. The optical laminate (c3) with a spacer has a layer structure of protective layer (HC layer) / liquid crystal polarizer (photo-alignment film (1) / cured layer) / overcoat layer / first laminating layer (adhesive layer (1)) / first liquid crystal phase difference layer (1) (cured layer (1-1)) / second laminating layer (adhesive layer (1)) / second liquid crystal phase difference layer (1) (cured layer (2-1)) / third laminating layer (adhesive layer (3)) / spacer.

[0495] [Comparative Example 4]

[0496] The outer coating side of the polarizing plate (1) with a substrate layer obtained above is subjected to a corona treatment. Next, the second substrate layer (PET film) on the first liquid crystal phase difference layer (2) side of the phase difference laminate (3) with a substrate layer obtained by the steps of Example 3 is peeled off, and the peeled surface is subjected to a corona treatment. During the peeling of the second substrate layer, the PET film is peeled off, and the photo-alignment film (2) is not peeled off and remains on the cured layer (1-2). The above-mentioned corona-treated surfaces are bonded to each other via the adhesive layer (1) obtained by peeling off the spacer of the adhesive layer (1) with a spacer on both sides.

[0497] Subsequently, the adhesive layer (3) exposed by peeling off one spacer from the adhesive layer (3) with spacers on both sides is laminated to the surface of the second liquid crystal retardation layer (2) with a substrate layer exposed by peeling off the second substrate layer (single-sided release-treated PET film), and the single-sided release-treated PET film on the side of the polarizing plate (1) with a substrate layer is peeled off to obtain an optical laminate (c4) with a spacer. By peeling off the second substrate layer, the single-sided release-treated PET film is peeled off, and the vertical alignment film is not oriented and remains on the cured product layer (2-2). The optical laminate (c4) with a spacer has a layer structure of protective layer (HC layer) / liquid crystal polarizer (photo-alignment film (1) / cured layer) / overcoat layer / first bonding layer (adhesive layer (1)) / first liquid crystal retardation layer (2) (photo-alignment film (2) / cured layer (1-2)) / second bonding layer (adhesive layer (1)) / second liquid crystal retardation layer (2) (cured layer (2-2) / vertical alignment film) / third bonding layer (adhesive layer (3)) / spacer.

[0498] [Comparative Example 5]

[0499] The first liquid crystal retardation layer (2) with a substrate layer obtained above and the second liquid crystal retardation layer (2) with a substrate layer are laminated via an active energy ray curable composition (2) in such a manner that the first liquid crystal retardation layer side (2) and the second liquid crystal retardation layer (2) side become the bonding surfaces. Next, ultraviolet rays are irradiated from the second liquid crystal retardation layer (2) side with a substrate layer to cure the active energy ray curable composition (2) to form a second bonding layer with a thickness of 2 μm, thereby obtaining a retardation laminate (c5) with a substrate layer.

[0500] An optical laminate (c5) with a spacer was obtained in the same manner as in Comparative Example 4 except that the phase difference laminate (c5) with a substrate layer was used instead of the phase difference laminate (3) with a substrate layer and the third bonding layer shown in Table 5 was used as the third bonding layer.

[0501] [Comparative Example 6]

[0502] An optical laminate (c6) with a spacer was obtained in the same manner as in Comparative Example 4 except that the laminate structure (c1) produced according to the procedure of Comparative Example 1 was used instead of the phase difference laminate (3) with a substrate layer and the third bonding layer shown in Table 5 was used as the third bonding layer.

[0503] [Calculation of the Thickness Ratio of the Adhesive Layer (Dt / D1)]

[0504] The distance from the surface of the protective layer on the opposite side to the liquid crystal polarizing plate to the surface of the third bonding layer on the opposite side to the second liquid crystal retardation layer is defined as D1 ( Figure 1), the total thickness of the layer (adhesive layer) with a Tg of 25°C or less in the first laminating layer, the second laminating layer, and the third laminating layer is set to Dt, and the thickness ratio [%] (=Dt / D1×100) is calculated. The cured layer of the active energy ray-curable composition (1) and the cured layer of the active energy ray-curable composition (2) were measured using the above-mentioned steps, and the results showed that both exceeded 25°C. In the embodiment, the total thickness Dt becomes the total thickness D2 of the thickness of the second laminating layer and the thickness of the third laminating layer. The results are shown in Tables 2 to 5.

[0505] [Wet heat test]

[0506] The optical laminate with spacers obtained above was cut into a size of 30 mm × 30 mm, and an alkali-free glass (EAGLE XG (registered trademark), 0.7 mm thick, manufactured by Corning) was laminated on the third laminating layer exposed by peeling off the spacers to prepare a test sample. The test sample was set in a spectrophotometer (V7100 manufactured by JASCO Corporation) so that the protective layer side became the incident surface, and the visibility-corrected transmittance of the transmitted light parallel to the transmission axis direction of the liquid crystal polarizer was measured, and the initial visibility-corrected transmittance Ty was taken. p 0.

[0507] Next, a damp heat test was conducted by placing the test sample in an oven set at a temperature of 65°C and a relative humidity of 90% for 500 hours, and then taking the test sample out of the oven. After that, the test sample was left at a temperature of 25°C and a relative humidity of 55% for 6 hours. The visibility-corrected transmittance of the transmitted light parallel to the transmission axis of the liquid crystal polarizer was measured for the test sample in the same manner as in the above step, and this was taken as the visibility-corrected transmittance Ty after the damp heat test. p 1. Calculate the visibility corrected transmittance Ty after the wet heat test p 1 and the initial visibility corrected transmittance Ty p 0 difference ΔTy p (=Ty p 1-Ty p 0), and evaluated according to the following criteria.

[0508] A: Difference ΔTy p It is greater than 0% and less than 1%.

[0509] B: Difference ΔTy p It is greater than 1% and less than 3%.

[0510] C: Difference ΔTy p More than 3%.

[0511] [Scratch test]

[0512] Using the optical laminate with a spacer obtained above, 1 hour after forming the second laminating layer and 30 minutes after forming the first laminating layer between the polarizing plate and the first liquid crystal phase difference layer, a test sample was prepared using the steps described in the above impact resistance test. A load of 5N was applied to the surface of the optical laminate side of the test sample (the surface on the protective layer side) using a scratch hardness tester (manufactured by German Eriksson, model 318, ball diameter 0.75mm), and the load was pushed while moving on the above surface at a speed of 1cm / s. Thereafter, under the conditions of the illumination of the fluorescent lamp and the reflected glare shown in Table 1, the protective layer side of the optical laminate of the test sample was observed from the front direction and the oblique direction, and the scratches were observed according to the criteria shown in the following Table 1. The results are shown in Tables 2 to 5. It should be noted that the following evaluations A to D are all within the allowable range for practical use.

[0513]

[0514] [Flexibility test (1): Evaluation of reflection color tone]

[0515] From the optical laminate with a spacer obtained above, a small rectangular test piece of 110 mm long side×10 mm short side was cut out using a supercutter so that the absorption axis of the liquid crystal polarizer was parallel to the long side.

[0516] like Figure 2 As shown in (a), in a bending tester having two independently movable clamps 501 and 502, the ends of the long sides of the test piece 500 are fixed to the clamps 501 and 502 with adhesive tapes, respectively, while the test piece 500 is bent so that the protective layer side of the test piece 500 is on the inside and the bending axis is parallel to the short side, and the positions of the clamps 501 and 502 are adjusted so that the interval L between the clamps 501 and 502 is 70 mm. Thereafter, as Figure 2As shown in (b), the jig 501 is moved in the direction of arrow A to further bend the test piece 500 so that the interval L is 4.0 mm (bending radius 2R). Thereafter, the jig 501 is moved in the direction of arrow B to restore the interval L to 70 mm. This series of actions is counted as one time, and the above actions are continuously repeated 100,000 times in an environment of temperature 25°C and relative humidity 55%. The moving speed of the jig 501 is 1.32 m / sec, and the time required to repeat the above action of changing the interval L 100,000 times is 27.8 hours. After repeating the above actions 100,000 times, the test piece 500 is taken out of the bending tester, the bending of the test piece 500 is released, the spacer is peeled off to expose the third bonding layer, and the aluminum-deposited film side of the PET film with aluminum-deposited film (manufactured by TORAY ADVANCED FILM, trade name "#50 DMS (X42)") is bonded to the exposed surface to form a bonded body. The laminate was observed from the front side of the protective layer to check the presence or absence of unevenness in the reflected color tone in the portion along the bending axis, and evaluated based on the following criteria. The results are shown in Tables 2 to 5.

[0517] A: Unevenness in reflected color tone is not observed.

[0518] B: Unevenness of reflected color tone is not noticeable, but can be observed.

[0519] C: Unevenness in reflected color tone is noticeable.

[0520] [Flexibility Test (2): Evaluation of Peeling of Third Lamination Layer]

[0521] From the optical laminate with spacers obtained above, a rectangular small piece with a long side of 110 mm and a short side of 10 mm was cut using a super cutter so that the absorption axis of the liquid crystal polarizer was parallel to the long side. The spacer was peeled off from the small piece to expose the third laminating layer, and the aluminum-deposited film side of a PET film with an aluminum-deposited film (manufactured by TORAY ADVANCED FILM, trade name "#50 DMS (X42)") was laminated to the exposed surface to prepare a test piece.

[0522] In addition to using this test piece, the bending tester used in the bending test (1) was used to repeat the action of changing the interval L 100,000 times under the conditions described in the bending test (1). After repeating the above action 100,000 times, the bending of the test piece taken out from the bending tester was released, and the presence or absence of peeling of the third bonding layer was confirmed from the front side of the protective layer of the test piece, and the evaluation was performed according to the following criteria. In the case where peeling occurred in the third bonding layer, since the peeling occurred from the end of the test piece, the size of the peeling was set to the shortest distance from the end of the test piece where the peeling occurred to the side of the test piece opposite to the end side where the peeling occurred. The results are shown in Tables 2 to 5.

[0523] A: No peeling of the third lamination layer was observed.

[0524] B: Peeling of the third bonding layer smaller than 100 μm was observed.

[0525] C: Peeling of the third bonding layer having a size of 100 μm or more was observed.

[0526] [Processability test]

[0527] A surface protective film was bonded to the protective layer side of the optical laminate with a spacer obtained above, and the surface protective film was cut into a rectangular shape so that the absorption axis of the liquid crystal polarizer was +45° relative to the long side to prepare a processing sample. The surface protective film was bonded to the protective layer so as to be peelable, and was a film that could be peeled off while maintaining the shape of the optical laminate with a spacer.

[0528] In the processability test, polishing was performed using an edge processing device to observe whether cracks of the first liquid crystal retardation layer and the second liquid crystal retardation layer were generated on the polished edge surfaces. Figure 3 The end surface processing device will be described. Figure 3: is a schematic three-dimensional diagram schematically showing an end surface processing device. In the end surface processing device, a device having a support portion 50 and two rotating tools 60 can be used to grind the stacked material W of the processing sample. The support portion 50 is a member for pressing the stacked material W from top and bottom and fixing it so that the stacked material W itself does not move during the grinding process and the stacked processing sample does not shift. The rotating tool 60 is a member for grinding the end surface of the stacked material W and can rotate around the rotation axis R. The support portion 50 can include a flat substrate (a moving mechanism for the stacked material W) 51; a door-shaped frame 52 arranged on the substrate 51; a rotating table 53 arranged on the substrate 51 and capable of rotating around the central axis; and a cylinder 54 that is arranged at a position of the frame 52 facing the rotating table 53 and can move up and down. The stacked material W is clamped and fixed by the rotating table 53 and the cylinder 54 via a clamp 55. Two rotating tools 60 are provided on both sides of the substrate 51 facing each other. The rotating tools 60 match the size of the stacked object W and can move in the direction along the rotation axis R, and the substrate 51 can move between the two rotating tools 60. During the grinding process, the stacked object W is fixed to the support portion 50, and after the position of the rotating tool 60 in the direction of the rotation axis is appropriately adjusted, the rotating tools 60 are rotated around their rotation axis R, and the substrate 51 is moved in a manner that the stacked object W passes between the rotating tools 60 facing each other. In this way, the following grinding process can be performed, that is, while the rotating tool 60 is relatively moved relative to the stacked object W in a direction parallel to the end face of the stacked object W and orthogonal to the stacking direction, the grinding blade of the rotating tool 60 is brought into contact with the exposed end faces of the stacked object W facing each other to grind these end faces.

[0529] use Figure 3 The end surface processing apparatus shown in the figure grinds the processing sample into a rectangle of 120 mm×50 mm (in plan view) under the grinding conditions shown below.

[0530] Number of samples to be laminated during grinding: 100

[0531] The clamping pressure of the laminate W that is pressed and polished from both sides: 0.1 MPa

[0532] Relative moving speed between the stack W and the rotating tool 60: 3500 mm / min

[0533] Rotation speed of the rotating tool 60: 5400 rpm

[0534] Feeding pitch (the value obtained by dividing the relative moving speed by the rotation speed of the rotating tool 60 and the number of times the grinding blade contacts the end surface when the rotating tool 60 rotates one circle): 0.32 mm

[0535] Grinding blade entry direction: The direction in which the grinding blade enters the end surface of the sample for processing from the spacer side toward the surface protection film side

[0536] The aluminum-deposited film side of a PET film with an aluminum-deposited film (manufactured by TORAY ADVANCED FILM, trade name "#50 DMS (X42)") was bonded to the third bonding layer exposed by peeling off the spacer from the processing sample after grinding to form a bonded body. The bonded body was evaluated from the protective layer side using an optical microscope VHX-1000 (manufactured by KEYENCE) according to the following criteria. The size of the crack was set to the diameter of the perfect circle inscribed in the crack when viewed from above the protective layer. The results are shown in Tables 2 to 5.

[0537] A: No cracks were observed.

[0538] B: Cracks with a size of less than 200 μm were observed.

[0539] C: Cracks with a size of 200 μm or more were observed.

[0540]

[0541]

[0542]

[0543]

[0544] Description of Reference Numerals

[0545] 1: optical laminate, 10: polarizing plate, 11: protective layer, 15: liquid crystal polarizer, 18: outer coating layer (second protective layer), 21: first liquid crystal phase difference layer, 22: second liquid crystal phase difference layer, 31: first bonding layer, 32: second bonding layer, 33: third bonding layer, 38: spacer, 50: supporting part, 51: substrate, 52: frame, 53: rotating table, 54: cylinder, 55: fixture, 60: rotating tool, 500: test piece, 501, 502: fixture, B: grinding blade, R: rotating axis, W: laminate.

Claims

1. An optical laminate, comprising, in order, a protective layer, a liquid crystal polarizing plate, a first laminating layer, a first liquid crystal phase difference layer, a second laminating layer, a second liquid crystal phase difference layer and a third laminating layer, The liquid crystal polarizer includes a cured layer of a first liquid crystal composition containing a dichroic dye and a polymerizable liquid crystal compound. The first liquid crystal retardation layer and the second liquid crystal retardation layer both include a cured layer of a second liquid crystal composition containing a polymerizable liquid crystal compound. The first laminating layer is a cured layer of an active energy ray-curable composition. The glass transition temperatures of the second bonding layer and the third bonding layer are both 25° C. or lower.

2. The optical layered body according to claim 1, wherein: The first bonding layer is a cured product layer of a radically polymerizable adhesive composition.

3. The optical layered body according to claim 1 or 2, wherein: The thickness of the protective layer, the liquid crystal polarizer, the first liquid crystal phase difference layer, and the second liquid crystal phase difference layer are all less than 20.0 μm.

4. The optical layered body according to claim 1 or 2, wherein: When the distance from the surface of the protective layer on the side opposite to the liquid crystal polarizer to the surface of the third bonding layer on the side opposite to the second liquid crystal retardation layer is D1, The total thickness D2 of the second bonding layer and the third bonding layer is not less than 40% and not more than 70% of D1, The units of D1 and D2 are μm. 5 . The optical laminate according to claim 1 , further comprising an overcoat layer covering the surface of the liquid crystal polarizing plate on the first bonding layer side.

Citation Information

Patent Citations

  • Laser light controlling device of measuring apparatus

    JP1991160317A

  • Compound, optical film, and manufacturing method for optical film

    JP2009173893A

  • Optical film, retardation film, elliptical polarizing plate, liquid crystal display device and compound

    JP2010244038A

  • Polycarbonate resin film, transparent film, and its forming method

    JP2012031370A

  • Polarization element, circularly polarizing plate and method of manufacturing those

    JP2013033249A